Organic thin film and method for producing the same, organic electroluminescent element and material thereof, photoelectric conversion element and material thereof
By using a pyridine ring structure compound with multi-dentate coordination capability in the electron injection layer of the organic EL element, the problem of insufficient electron injection and transportability in the prior art is solved, and more efficient electron injection and transport is achieved, and the life of the element is extended.
Patent Information
- Application Number
- CN202080062573.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-04-03
- Filing Date
- 2020-09-04
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2040-09-04
AI Technical Summary
The electron injection and electron transportability of existing organic electroluminescent (EL) components are insufficient, affecting the performance and life of the components.
Compounds with specific structures having more than two pyridine rings in the skeleton are used as materials for the electron injection layer. These compounds have high electron donation and multi-dentate coordination capabilities, can coordinate with inorganic materials and form hydrogen bonds, and improve electron injection properties.
Excellent electron injection and electron transport properties are achieved, extending the life of organic EL components, and simplifying the manufacturing process.
Smart Images

Figure FHA0000008280120000011 
Figure FHA0000008280120000021 
Figure FHA0000008280120000022
Abstract
Description
Technical Field
[0001] The present invention relates to an organic thin film and a method for producing an organic thin film, an organic electroluminescent (hereinafter sometimes referred to as "EL") element, a display device, a lighting device, an organic thin film solar cell, a thin film transistor, a photoelectric conversion element, a coating composition, and a material for an organic electroluminescent element. Background Art
[0002] Organic EL elements are thin, soft and flexible. In addition, compared with the current mainstream liquid crystal display devices and plasma display devices, display devices using organic EL elements can achieve high brightness and high-definition display. In addition, compared with liquid crystal display devices, display devices using organic EL elements have a wide viewing angle. Therefore, for display devices using organic EL elements, it is expected that the application of such as display screens for televisions and mobile phones will be expanded in the future.
[0003] In addition, the application of organic EL elements as lighting devices is also expected.
[0004] An organic EL element is formed by stacking a cathode, a light-emitting layer, and an anode. In an organic EL element, the energy difference between the work function of the anode and the highest occupied molecular orbital (HOMO) of the light-emitting layer is smaller than the energy difference between the work function of the cathode and the lowest unoccupied molecular orbital (LUMO) of the light-emitting layer. Therefore, it is more difficult to inject electrons from the cathode into the light-emitting layer than to inject holes from the anode into the light-emitting layer. Therefore, in existing organic EL elements, an electron injection layer is arranged between the cathode and the light-emitting layer to promote the injection of electrons from the cathode into the light-emitting layer. In addition, a scheme for improving electron injection / transport properties by doping a dopant in a layer arranged between the cathode and the light-emitting layer has also been proposed (for example, see non-patent document 1 and non-patent document 2).
[0005] As the electron injection layer of the organic EL element, an inorganic oxide layer can be mentioned (for example, see Non-Patent Document 3). However, the electron injection property of the inorganic oxide layer is not sufficient.
[0006] There is also a technology for improving the electron injection property of an organic EL element by further forming an electron injection layer on an inorganic oxide layer. For example, non-patent document 4 describes an organic EL element having an electron injection layer composed of polyethyleneimine. In addition, non-patent document 5 describes that amines are effective in improving the injection rate of electrons. Non-patent documents 6, 7, 8, and 12 describe the effect of amino groups on electron injection at the interface between the electrode and the organic layer. In addition, regarding phenanthroline derivatives, non-patent documents 10 to 11 report that they promote the release of electrons from metal atoms through their high coordination ability with metal ions and greatly reduce the electron injection barrier at the electrode / organic layer interface. The operation of forming an organic thin film composed only of phenanthroline derivatives at the interface between the electrode and the organic layer has been widely carried out. In addition, patent document 1 discloses an organic EL element, which uses a phenanthroline compound as an electron transporting main material, and dopes an inert metal in the main material, thereby reducing the energy level of the LUMO of the electron transporting material, promoting electron injection, and reducing the driving voltage of the element. An organic EL element is also disclosed, in which a compound having an amino group bonded directly or via another group to a group derived from an electron transporting compound, or an organic material having an acid dissociation constant pKa of 1 or more is used as a material for an electron injection layer (see Patent Documents 2 to 4).
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: International Publication No. 2017 / 211100
[0010] Patent Document 2: Japanese Patent Application Publication No. 2017-157743
[0011] Patent Document 3: Japanese Patent Application Publication No. 2019-176093
[0012] Patent Document 4: Japanese Patent Application Publication No. 2019-179863
[0013] Non-patent literature
[0014] Non-patent document 1: Karsten Walzer et al., "Chemical Review", Vol. 107, 2007, pp. 1233-1271
[0015] Non-patent document 2: Peng Wei et al., Journal of the American Chemical Society, Vol. 132, 2010, p. 8852
[0016] Non-patent document 3: Jiangshan Chen et al., Journal of Materials Chemistry, Vol. 22, 2012, pp. 5164-5170
[0017] Non-patent document 4: Hyosung Choi et al., "Advanced Materials", Vol. 23, 2011, p. 2759
[0018] Non-patent document 5: Yinhua Zho and 21 others, "Science", Vol. 336, 2012, p. 327
[0019] Non-patent document 6: Young-Hoon Kim et al., “Advanced Functional Materials”, 2014, DOI: 10.1002 / adfm.201304163
[0020] Non-patent document 7: Stefan Hofle et al., “Advanced Materials”, 2014, DOI: 10.1002 / adma.201304666
[0021] Non-patent document 8: Stefan Hofle and five others, Advanced Materials, Vol. 26, 2014, DOI: 10.1002 / adma.201400332
[0022] Non-patent document 9: Peng Wei et al., Journal of the American Chemical Society, Vol. 132, 2010, p. 8852
[0023] Non-patent document 10: Hiroyuki Yoshida, “J. Phys. Chem. C20151194324459-24464”, Vol. 119, 2015, p. 24459
[0024] Non-Patent Literature 11: Zhengyang Bin and seven others, “Nature Communications”, Vol. 10, 2019, p. 866
[0025] Non-Patent Literature 12: Hirohiko Fukagawa et al., “Advanced Materials”, Vol. 31, 2019, p. 1904201 Summary of the invention
[0026] Problems to be solved by the invention
[0027] However, there is a demand for further improvement in electron injection properties and electron transport properties in conventional organic EL devices including an electron injection layer.
[0028] The present invention has been completed in view of the above situation, and its subject is to provide an organic film that can obtain excellent electron injection and electron transport properties when used as an electron injection layer of an organic EL element, a coating composition that can be suitable for use in the manufacture of the organic film, and a material for an organic EL element that serves as a raw material for these organic films or coating compositions.
[0029] Another object of the present invention is to provide an organic EL element using the organic thin film of the present invention, a display device and a lighting device having the organic EL element, and an organic thin film solar cell, a photoelectric conversion element, and an organic thin film transistor including the organic thin film of the present invention.
[0030] Means for solving problems
[0031] As materials used in the electron injection layer of an organic EL element, the inventors have focused on organic materials that can be multidentately coordinated and have electron-donating nitrogen atoms in a heterocyclic ring. As a result, it is known that an organic thin film containing a compound having a specific structure with two or more pyridine rings in the skeleton and an electron-transporting material can be used as the electron injection layer of an organic EL element.
[0032] That is, due to the high electron donating property of the nitrogen atom contained in the compound represented by the general formula (1) of the present invention, in addition to the effect of improving the electron injection property brought about by the coordination interaction with the inorganic material, when there are other organic materials (materials that transport electrons) adjacent to the organic material, the nitrogen atom can form hydrogen bonds with the organic material and provide a trace amount of charge, thereby generating negative charge on the side of the other organic material. It is speculated that this is also the reason for the improvement of the electron injection property.
[0033] The present invention has been accomplished based on the above-mentioned technical idea, and the gist of the present invention is as follows.
[0034] [1] An organic thin film characterized in that it is a single-layer film comprising a first material and a second material that transports electrons, or a laminated film comprising a film comprising the first material and a film comprising the second material, wherein the first material is a compound having a structure represented by the following general formula (1).
[0035] [Chemistry 1]
[0036]
[0037] (In general formula (1), X1 , X 2 are the same or different and represent a nitrogen atom, an oxygen atom, a sulfur atom or a divalent linking group which may or may not have a substituent. L represents a direct bond or a p-valent linking group. n represents a number of 0 or 1, and p represents a number of 1 to 4. q represents a number of 0 or 1, and when p is 1, q is 0. R 1 ~R 3 The same or different, represents a monovalent substituent. 1 ~m 3 Same or different, represents a number from 0 to 3. )
[0038] [2] The organic thin film according to [1], wherein the first material is a compound wherein n is 0 in the general formula (1).
[0039] [3] A laminated film comprising an oxide layer and the organic thin film layer according to [1] or [2] formed on the oxide layer.
[0040] [4] An organic electroluminescent element having a light-emitting layer between a cathode and an anode, characterized in that the organic thin film described in [1] or [2] or the laminated film described in [3] is provided between the cathode and the light-emitting layer.
[0041] [5] The organic electroluminescent element according to [4], characterized in that an inorganic oxide layer is provided between the cathode and the organic thin film.
[0042] [6] The organic electroluminescent element described in [4] or [5] is characterized in that a laminated film of a film containing the first material and the second material and a film containing the second material is provided between the cathode and the light-emitting layer.
[0043] [7] The organic electroluminescent element according to [6], characterized in that a layer containing the second material is provided between the light-emitting layer and the film containing the first material and the second material.
[0044] [8] The organic electroluminescent element according to [6], characterized in that a layer containing the second material is provided between the cathode and the film containing the first material and the second material.
[0045] [9] The organic electroluminescent element according to any one of [4] to [8], characterized in that a layer containing the second material is provided between the anode and the light-emitting layer.
[0046]
[10] The organic electroluminescent element according to any one of [4] to [9], wherein the light-emitting layer contains the second material.
[0047]
[11] A material for an organic electroluminescent device, comprising a phenanthroline compound having a structure represented by the following general formula (2).
[0048] [Chemistry 2]
[0049]
[0050] (In general formula (2), R 4 , R 5 The same or different, represents a dialkylamino group or an alkoxy group. 4 、m 5 Same or different, representing a number of 1 or 2. )
[0051]
[12] An organic electroluminescent element having a light-emitting layer between a cathode and an anode, characterized in that a layer containing the material for an organic electroluminescent element described in
[11] is present between the cathode and the anode.
[0052]
[13] The organic electroluminescent element described in
[12] is characterized in that a layer containing the material for an organic electroluminescent element described in
[11] is provided between the cathode and the light-emitting layer.
[0053]
[14] The organic electroluminescent element described in
[12] or
[13] , characterized in that an inorganic oxide layer is provided between the cathode and the layer containing the material for an organic electroluminescent element described in
[11] .
[0054]
[15] A display device comprising the organic electroluminescent element according to any one of [4] to
[10] and
[12] to
[14] .
[0055]
[16] A lighting device comprising the organic electroluminescent element according to any one of [4] to
[10] and
[12] to
[14] .
[0056]
[17] A material for an organic thin-film solar cell, characterized in that it contains a phenanthroline compound having a structure represented by the following general formula (2).
[0057] [Chemistry 3]
[0058]
[0059] (In general formula (2), R 4 , R 5 The same or different, represents a dialkylamino group or an alkoxy group. 4 、m 5 Same or different, representing a number of 1 or 2. )
[0060]
[18] An organic thin film solar cell, characterized in that it comprises any one of the organic thin film described in [1] or [2], the laminated film described in [3], or a layer comprising the material for an organic thin film solar cell described in
[17] .
[0061]
[19] A photoelectric conversion element material, comprising a phenanthroline compound having a structure represented by the following general formula (2).
[0062] [Chemistry 4]
[0063]
[0064] (In general formula (2), R 4 , R 5 The same or different, represents a dialkylamino group or an alkoxy group. 4 、m 5 Same or different, representing a number of 1 or 2. )
[0065]
[20] A photoelectric conversion element, characterized in that it comprises any one of the organic thin film described in [1] or [2], the laminated film described in [3], or the layer containing the photoelectric conversion element material described in
[19] .
[0066]
[21] A material for a thin film transistor, characterized in that it contains a phenanthroline compound having a structure represented by the following general formula (2).
[0067] [Chemistry 5]
[0068]
[0069] (In general formula (2), R 4 , R 5 The same or different, represents a dialkylamino group or an alkoxy group. 4 、m 5 Same or different, representing a number of 1 or 2. )
[0070]
[22] A thin film transistor, characterized in that it comprises any one of the organic thin film described in [1] or [2], the laminated film described in [3], or a layer comprising the material for a thin film transistor described in
[21] .
[0071]
[23] A coating composition comprising a first material which is a compound having a structure represented by the following general formula (1) and a second material which transports electrons.
[0072] [Chemistry 6]
[0073]
[0074] (In general formula (1), X1 , X 2 are the same or different and represent a nitrogen atom, an oxygen atom, a sulfur atom or a divalent linking group which may or may not have a substituent. L represents a direct bond or a p-valent linking group. n represents a number of 0 or 1, and p represents a number of 1 to 4. q represents a number of 0 or 1, and when p is 1, q is 0. R 1 ~R 3 The same or different, represents a monovalent substituent. 1 ~m 3 Same or different, represents a number from 0 to 3. )
[0075]
[24] A coating composition, characterized in that it contains a first material, wherein the first material is a compound having a structure represented by the following general formula (1).
[0076] [Chemistry 7]
[0077]
[0078] (In general formula (1), X 1 , X 2 are the same or different and represent a nitrogen atom, an oxygen atom, a sulfur atom or a divalent linking group which may or may not have a substituent. L represents a direct bond or a p-valent linking group. n represents a number of 0 or 1, and p represents a number of 1 to 4. q represents a number of 0 or 1, and when p is 1, q is 0. R 1 ~R 3 The same or different, represents a monovalent substituent. 1 ~m 3 Same or different, represents a number from 0 to 3. )
[0079]
[25] A method for manufacturing an organic thin film, characterized in that it includes the following steps: a step of forming a single-layer film on a formed surface, wherein the single-layer film comprises a first material and a second material for transmitting electrons, wherein the first material is a compound having a structure represented by the following general formula (1); or a step of sequentially forming a film comprising the first material and a film comprising the second material on a formed surface.
[0080] [Chemistry 8]
[0081]
[0082] (In general formula (1), X 1 , X 2 are the same or different and represent a nitrogen atom, an oxygen atom, a sulfur atom or a divalent linking group which may or may not have a substituent. L represents a direct bond or a p-valent linking group. n represents a number of 0 or 1, and p represents a number of 1 to 4. q represents a number of 0 or 1, and when p is 1, q is 0. R 1 ~R 3The same or different, represents a monovalent substituent. 1 ~m 3 Same or different, represents a number from 0 to 3. )
[0083]
[26] A method for manufacturing an organic thin film, characterized in that it includes a step of forming a film containing a first material on a surface to be formed, wherein the first material is a compound having a structure represented by the following general formula (1).
[0084] [Chemistry 9]
[0085]
[0086] (In general formula (1), X 1 , X 2 are the same or different and represent a nitrogen atom, an oxygen atom, a sulfur atom or a divalent linking group which may or may not have a substituent. L represents a direct bond or a p-valent linking group. n represents a number of 0 or 1, and p represents a number of 1 to 4. q represents a number of 0 or 1, and when p is 1, q is 0. R 1 ~R 3 The same or different, represents a monovalent substituent. 1 ~m 3 Same or different, represents a number from 0 to 3. )
[0087]
[27] The method for producing an organic thin film as described in
[26] is characterized in that the above-mentioned formed surface contains a second material.
[0088] Effects of the Invention
[0089] The organic thin film of the present invention comprises a first material composed of a specific organic material having electron donating properties and a second material that transports electrons. Therefore, when the organic thin film of the present invention is used, for example, in an electron injection layer of an organic EL element, excellent electron injection properties and electron transport properties can be obtained, and the life of the organic EL element can be extended.
[0090] The organic EL device of the present invention has the organic thin film of the present invention between the cathode and the light-emitting layer. Therefore, excellent electron injection and electron transport properties can be obtained through the organic thin film, and the life of the organic EL device can be extended.
[0091] In addition, the organic thin film of the present invention comprises a first material composed of a compound having a specific structure with two or more pyridine rings in the skeleton (which is an organic material capable of multidentate coordination containing an electron-donating nitrogen atom in a heterocyclic ring) and a second material that transmits electrons, and the organic thin film can be formed by any method of coating and vapor deposition. Therefore, there are few process restrictions when manufacturing an organic EL element including the organic thin film of the present invention, and it is easy to use as a material for a layer constituting an organic EL element. The method for manufacturing an organic thin film of the present invention is a method for manufacturing such an organic thin film of the present invention.
[0092] The coating composition of the present invention comprises a first material composed of a specific organic material capable of multidentate coordination containing an electron-donating nitrogen atom in a heterocyclic ring and a second material capable of transporting electrons. Therefore, by applying the coating composition of the present invention on a surface on which an organic thin film is to be formed, an organic thin film suitable for an electron injection layer of an organic EL element can be obtained.
[0093] The material for organic EL device of the present invention is a useful material used in the organic thin film or coating composition of the present invention for the production of organic EL devices, etc. In addition, the material can be used alone as an electron injection layer or an electron transport layer, and is also a useful material in this respect.
[0094] Since the display device and the lighting device of the present invention include the organic EL element of the present invention, they have low driving voltage and excellent characteristics.
[0095] Furthermore, the organic thin-film solar cell, the photoelectric conversion element, and the organic thin-film transistor of the present invention include the organic thin film of the present invention and therefore have excellent characteristics. BRIEF DESCRIPTION OF THE DRAWINGS
[0096] Figure 1 This is a diagram showing the electrostatic potential of a phenanthroline derivative calculated using quantum chemical calculation.
[0097] Figure 2 This is a diagram showing the most stable structure, the highest occupied molecular orbital, and ionization energy in a phenanthroline derivative and triphenylamine two-molecule system calculated using quantum chemical calculations.
[0098] Figure 3 The results are for the state where only the boron compound exists, and the state where the boron compound and phenanthroline coexist. 1 A diagram comparing H-NMR measurement results.
[0099] Figure 4 This is a schematic cross-sectional view for explaining an example of the organic EL element of the present invention.
[0100] Figure 5 This is a schematic cross-sectional view for explaining an example of the organic EL element of the present invention.
[0101] Figure 6 This is a schematic cross-sectional view showing another example of the layered structure of the organic EL element of the present invention.
[0102] Figure 7 This is a schematic cross-sectional view showing another example of the layered structure of the organic EL element of the present invention.
[0103] Figure 8-1 This is a schematic cross-sectional view showing an example of the organic thin film of the present invention.
[0104] Figure 8-2 This is a schematic cross-sectional view showing an example of the organic thin film of the present invention.
[0105] Figure 9-1 This is a schematic cross-sectional view showing an example of the layered structure of the organic thin film of the present invention.
[0106] Figure 9-2 This is a schematic cross-sectional view showing an example of the layered structure of the organic thin film of the present invention.
[0107] Figure 10-1 This is a schematic cross-sectional view showing an example of the layered structure of the organic thin film of the present invention.
[0108] Figure 10-2 This is a schematic cross-sectional view showing an example of the layered structure of the organic thin film of the present invention.
[0109] Figure 11-1 This is a schematic cross-sectional view showing an example of the layered structure of the organic thin film of the present invention.
[0110] Figure 11-2 This is a schematic cross-sectional view showing an example of the layered structure of the organic thin film of the present invention.
[0111] Figure 12-1 This is a schematic cross-sectional view showing an example of the layered structure of the organic thin film of the present invention.
[0112] Figure 12-2 This is a schematic cross-sectional view showing an example of the layered structure of the organic thin film of the present invention.
[0113] Figure 13-1 This is a schematic cross-sectional view showing an example of the layered structure of the organic thin film of the present invention.
[0114] Figure 13-2 This is a schematic cross-sectional view showing an example of the layered structure of the organic thin film of the present invention.
[0115] Figure 14-1 This is a schematic cross-sectional view showing an example of the layered structure of the organic thin film of the present invention.
[0116] Figure 14-2 This is a schematic cross-sectional view showing an example of the layered structure of the organic thin film of the present invention.
[0117] Fig.15 This is a graph showing the relationship between the applied voltage and the luminance of the organic EL elements of Examples 1 and 2 and Comparative Example 1.
[0118] Fig.16 This is a graph showing the relationship between the applied voltage and the current density of the organic EL elements of Examples 1 and 2 and Comparative Example 1.
[0119] Fig.17 This is a graph showing the relationship between the current density and the external quantum efficiency of the organic EL elements of Examples 1 and 2 and Comparative Example 1.
[0120] Fig.18 This is a graph showing the relationship between the applied voltage and the luminance of the organic EL elements of Examples 3 to 5 and Comparative Example 2.
[0121] Fig.19 This is a graph showing the relationship between the applied voltage and the current density of the organic EL elements of Examples 3 to 5 and Comparative Example 2.
[0122] Fig. 20 This is a graph showing the relationship between the current density and the external quantum efficiency of the organic EL elements of Examples 3 to 5 and Comparative Example 2.
[0123] Fig.21 This is a graph showing the relationship between the applied voltage and the luminance of the organic EL elements of Examples 6 and 7 and Comparative Example 2.
[0124] Fig. 22 This is a graph showing the relationship between the applied voltage and the current density of the organic EL elements of Examples 6 and 7 and Comparative Example 2.
[0125] Fig.23 This is a graph showing the relationship between the current density and the external quantum efficiency of the organic EL elements of Examples 6 and 7 and Comparative Example 2.
[0126] Fig.24 This is a graph showing the relationship between the continuous driving time and the luminance of the organic EL elements of Examples 6 and 7.
[0127] Fig.25 This is a graph showing the relationship between the applied voltage and the luminance of the organic EL elements of Examples 1 and 8.
[0128] Fig.26 This is a graph showing the relationship between the applied voltage and the current density of the organic EL elements of Examples 1 and 8.
[0129] Fig. 27This is a graph showing the relationship between the current density and the external quantum efficiency of the organic EL elements of Examples 1 and 8.
[0130] Fig.28 This is a graph showing the relationship between the continuous driving time and the luminance of the organic EL elements of Examples 1 and 8.
[0131] Fig.29 This is a graph showing the relationship between the applied voltage and the luminance of the organic EL elements of Examples 9 to 13 and Comparative Example 3.
[0132] Fig.30 The diagram shows a microscopic image of the light emitting surface when the organic EL elements of Examples 12 and 13 and Comparative Example 3 were stored in the atmosphere without being sealed.
[0133] Fig.31 This is a graph showing the relationship between the applied voltage and the luminance of the organic EL elements of Example 14 and Comparative Example 4.
[0134] Fig.32 Graph showing the relationship between the continuous driving time and the luminance of the organic EL elements of Example 14 and Comparative Example 4.
[0135] Fig.33 This is a graph showing the relationship between the applied voltage and the luminance of the organic EL elements of Example 15 and Comparative Example 5.
[0136] Fig.34 This is a graph showing the relationship between the applied voltage and the luminance of the organic EL elements of Example 16 and Comparative Example 6.
[0137] Fig.35 This is a graph showing the relationship between the applied voltage and the luminance of the organic EL elements of Examples 17 to 20 and Comparative Example 7.
[0138] Fig.36 This is a graph showing the relationship between the applied voltage and the luminance of the organic EL elements of Example 21 and Comparative Example 8. DETAILED DESCRIPTION
[0139] The present invention is described in detail below.
[0140] "Materials for organic thin films and organic EL devices"
[0141] The organic thin film of the present invention comprises a first material and a second material, wherein the first material is a compound having a structure represented by the following general formula (1), and the second material is a material that transports electrons and is different from the first material. The organic thin film of the present invention may be a single-layer film comprising the first material and the second material, or may be a laminated film in which a layer comprising the first material and a layer comprising the second material are laminated.
[0142] [Chemistry 10]
[0143]
[0144] (In general formula (1), X 1 , X 2 are the same or different and represent a nitrogen atom, an oxygen atom, a sulfur atom or a divalent linking group which may or may not have a substituent. L represents a direct bond or a p-valent linking group. n represents a number of 0 or 1, and p represents a number of 1 to 4. q represents a number of 0 or 1, and when p is 1, q is 0. R 1 ~R 3 The same or different, represents a monovalent substituent. 1 ~m 3 Same or different, represents a number from 0 to 3. )
[0145] The first material constituting the organic thin film of the present invention is a material that can be multidentate coordinated and contains an electron-donating nitrogen atom in a heterocyclic ring, so that a hydrogen bond is stably formed between the first material and the second material, and the material has the ability to generate negative charges on the second material side. The first material preferably has a large negative electrostatic potential at the nitrogen site serving as the electron-donating portion. The larger the electrostatic potential of the first material, the higher the ability to generate negative charges on the second material side. In addition, it has been confirmed that the material has the effect of increasing the life of the element.
[0146] Therefore, the organic thin film of the present invention can be used not only for elements composed of organic compounds alone, but also for elements composed of organic compounds and inorganic compounds, and can improve electron injection properties and atmospheric stability, thereby achieving the effect of extending the life of the element.
[0147] One of the characteristics of the organic film of the present invention is that it contains a compound having a structure represented by the above general formula (1) as the first material. When the organic film of the present invention is used for an electron injection layer, excellent electron injection and electron transport properties can be obtained. Such a compound having a structure represented by the above general formula (1) is a compound suitable as a material for an organic EL element. The phenanthroline compound represented by the above general formula (2) is contained in the above general formula (1), and an organic EL element material containing such a phenanthroline compound represented by the above general formula (2) is also one of the present invention.
[0148] It should be noted that the "electrostatic potential" described in the present invention can be calculated using, for example, a quantum chemical calculation program such as GAUSSIAN. Although the absolute amount of the calculated value varies depending on the basis function used in the calculation, etc., the relative value of the magnitude calculated by the same calculation method can be used to discuss the correlation between the electrostatic potential and the amount of negative charge generated.
[0149] As an example of the first material of the present invention, the electrostatic potential of the nitrogen site in phenanthroline contained in various first materials was calculated under the following conditions.
[0150] Functions used in calculation of the most stable structures of phenanthroline compounds
[0151] B3LYP / 6-31+G(d)
[0152] Functions used in the calculation of electrostatic potentials of phenanthroline compounds
[0153] B3LYP / 6-311++G(2df,2p)
[0154] The calculation results are shown in Figure 1 . The calculated value of the electrostatic potential of the portion of phenanthroline surrounded by the dotted line close to the coordinating nitrogen atom in the most basic skeleton is shown. For other compounds 1 to 13, the values of the electrostatic potential are also the values of the same portion as phenanthroline. Figure 1 As shown, the value of the electrostatic potential depends strongly on the substituents imparted to phenanthroline.
[0155] Large electrostatic potential values are obtained in compound 1 endowed with a pyrrolidinyl group as an electron-donating substituent, compound 2 endowed with a dimethylamino group as an electron-donating substituent, and compound 3 endowed with a methoxy group as an electron-donating substituent. These compounds increase the electron density of the phenanthroline skeleton through the electron-donating substituents, which can increase the hydrogen bonding ability of the nitrogen atom and the coordination ability to inorganic compounds, and are therefore particularly suitable as the first material.
[0156] In addition, regarding compounds represented by the general formula (1) other than phenanthroline, when n is 1, the number of nitrogen atoms participating in hydrogen bonding and coordination with the inorganic compound is large, and therefore it is considered that the value of the electrostatic potential is relatively large.
[0157] Apart from Figure 1 In addition to the compounds having only one phenanthroline group shown in the foregoing, compounds having two or more phenanthrolines as shown in the following formulae (3-1) to (3-4) are also considered to be effective for generating negative charges and are suitable as the first material.
[0158] [Chemistry 11]
[0159]
[0160] The generation of negative charges caused by phenanthroline derivatives was also simulated using quantum chemical calculations. The results are shown in Figure 2 Various phenanthroline derivatives were used as the first material, and triphenylamine (TPA) having a simple molecular structure was used as the second material. The optimized structures of the two molecules were calculated, and the ionization energy of triphenylamine in the optimized structure was calculated.
[0161] like Figure 2As shown in FIG. 1 , in the optimized structure, a specific hydrogen of triphenylamine forms a hydrogen bond with nitrogen of phenanthroline, and a change in ionization energy is observed. Although the distribution of the highest occupied orbital does not change in the calculation of the two molecules, it is known that the ionization energy becomes smaller when a phenanthroline derivative with a larger electrostatic potential value is used.
[0162] The reduction in ionization energy means that electrons can be easily extracted from triphenylamine molecules, that is, triphenylamine can be easily negatively charged. The larger the electrostatic potential of the first material, the more negative charges can be generated in the second material.
[0163] Figure 3 shown 1 H-NMR measurements suggested the presence of hydrogen bonds.
[0164] A simple boron compound was used for the measurement, and the positions of the proton peaks in the case of the boron compound alone and the proton peaks in the state where phenanthroline coexists were compared.
[0165] The amount of phenanthroline added was 5 molar equivalents relative to the boron compound, and the measurement was performed in deuterated chloroform. Figure 3 It is known that the peak position of the proton enclosed in the frame is shifted to the high magnetic field side. This is because the boron compound and phenanthroline interact with each other through hydrogen bonding, thereby increasing the electron density of hydrogen atoms in the boron compound.
[0166] In the above general formula (1), X 1 , X 2 The same or different means a nitrogen atom, an oxygen atom, a sulfur atom or a divalent linking group which may or may not have a substituent.
[0167] Examples of the divalent linking group include a divalent hydrocarbon group and a group in which a part of carbon atoms of the hydrocarbon group is substituted with a hetero atom selected from the group consisting of a nitrogen atom, an oxygen atom and a sulfur atom.
[0168] The hydrocarbon group is preferably a hydrocarbon group having 1 to 6 carbon atoms, and more preferably a hydrocarbon group having 1, 2 or 6 carbon atoms.
[0169] The hydrocarbon group may be linear, branched, cyclic, or a combination thereof.
[0170] The divalent hydrocarbon group may be an alkylene group which is a saturated hydrocarbon group, or may be an unsaturated hydrocarbon group such as an alkenylene group or an alkynylene group.
[0171] Specifically, the divalent hydrocarbon group is preferably a group represented by the following formulae (4-1) to (4-4). In the following formulae, R in (4-1) to (4-4) represents a substituent. X, including R in (4-1) to (4-4), is 1 , X 2Specific examples of the substituent in can include the following R 1 ~R 3 The same group as the monovalent substituent of .
[0172] [Chemistry 12]
[0173]
[0174] L in the above general formula (1) represents a direct bond or a p-valent linking group. It should be noted that L is a direct bond only when p is 2.
[0175] Examples of the p-valent linking group include, in addition to nitrogen atoms, oxygen atoms, sulfur atoms and carbon atoms, groups obtained by removing p hydrogen atoms from a hydrocarbon group or a group in which a portion of the carbon atoms of the hydrocarbon group are substituted with any hetero atom of nitrogen atoms, oxygen atoms and sulfur atoms.
[0176] When the p-valent linking group is a group having carbon atoms, it is preferably a group having 1 to 30 carbon atoms, and more preferably a group having 1 to 20 carbon atoms.
[0177] The hydrocarbon group may be linear, branched, cyclic, or a combination thereof.
[0178] The hydrocarbon group may be any of a saturated hydrocarbon group, an unsaturated hydrocarbon group, and an aromatic hydrocarbon group.
[0179] Examples of the aromatic hydrocarbon group include groups obtained by removing a hydrogen atom from an aromatic compound, such as a benzene ring, a naphthalene ring, an anthracene ring, a tetracene ring, a pentacene ring, a triphenylene ring, a pyrene ring, a fluorene ring and an indene ring.
[0180] In the above general formula (1), R 1 ~R 3 The same or different groups represent a monovalent substituent.
[0181] Examples of the monovalent substituent include: a fluorine atom; a halogenated alkyl group such as a fluoromethyl group, a difluoromethyl group, and a trifluoromethyl group; a linear or branched alkyl group having 1 to 20 carbon atoms such as a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, and a tert-butyl group; a cyclic alkyl group having 5 to 7 carbon atoms such as a cyclopentyl group, a cyclohexyl group, and a cycloheptyl group; and a methoxy group, an ethoxy group, a propoxy group, an isopropoxy group, a butoxy group, an isobutoxy group, a tert-butoxy group, a pentyloxy group, a hexyloxy group, a heptyloxy group, and an octyloxy group. 20; a straight-chain or branched alkoxy group; a nitro group; a cyano group; an alkylamino group having an alkyl group having 1 to 10 carbon atoms, such as methylamino, ethylamino, dimethylamino, and diethylamino; a cyclic amino group such as pyrrolidinyl, piperidinyl, and morpholinyl; a diarylamino group such as diphenylamino and carbazolyl; an acyl group such as acetyl, propionyl, and butyryl; an alkenyl group having 2 to 30 carbon atoms, such as styryl; an aryl group having 5 to 20 carbon atoms (specific examples of the aryl group are the same as the above-mentioned aromatic hydrocarbon group) which may be substituted with a halogen atom such as fluorine atom or an alkyl group, alkoxy group, and amino group having 1 to 20 carbon atoms, and having 4 to 20 carbon atoms and containing at least one of a nitrogen atom, a sulfur atom, and an oxygen atom, which may be substituted with a halogen atom such as fluorine atom or an alkyl group, alkoxy group, and amino group having 1 to 20 carbon atoms (the heterocyclic group may be composed of only one ring, or may be a compound composed of only one aromatic heterocyclic ring to which a plurality of atoms are directly bonded via one carbon atom, or may be a compound composed of a plurality of atoms directly bonded to each other ... The condensed heterocyclic group. Specific examples of the heterocyclic group include thiophene ring, furan ring, pyrrole ring, benzothiophene ring, benzofuran ring, indole ring, dibenzothiophene ring, dibenzofuran ring, carbazole ring, thiazole ring, benzothiazole ring, oxazole ring, benzoxazole ring, imidazole ring, benzimidazole ring, pyridine ring, pyrimidine ring, pyrazine ring, pyridazine ring, triazine ring, quinoline ring, isoquinoline ring, quinoxaline ring, benzothiadiazole ring, phenanthridine ring (specific examples of aromatic heterocyclic groups); ester group, thioether group, etc. It should be noted that these groups may also be substituted by halogen atoms, heteroelements, alkyl groups, aromatic rings, etc.
[0182] In the above general formula (2), R 4 , R 5 The same or different groups represent dialkylamino or alkoxy groups.
[0183] As the dialkylamino group, a group having an alkyl group having 1 to 20 carbon atoms, such as a methyl group or an ethyl group, is preferred. A group having an alkyl group having 1 to 10 carbon atoms is more preferred. In addition, the carbon number of the two alkyl groups of the dialkylamino group may be the same or different. In addition, an amino group having two alkyl groups linked together, such as a cyclic amino group such as a piperidinyl group, a pyrrolidinyl group, or a morpholinyl group, is also preferred.
[0184] Examples of the alkoxy group include those having the same structure as R in the general formula (1): 1 ~R 3 The same applies to alkoxy groups.
[0185] In the general formula (1), p represents a number of 1 to 4, and preferably a number of 1 to 3. Specific examples of the compound in which p in the general formula (1) is 1 include compounds represented by the following formulae (5-1) to (5-9).
[0186] [Chemistry 13]
[0187]
[0188] In the general formula (1), n represents a number of 0 or 1, and the compound represented by the general formula (1) is a compound in which n is 0, which is one of the preferred embodiments of the present invention. Specific examples of the compound in which n is 0 in the general formula (1) include compounds represented by the formulas (5-1) to (5-6).
[0189] The second material in the present invention can be any material that transmits electrons, and is preferably an organic material. More preferably, an organic material having a lowest unoccupied molecular orbital (LUMO) energy level of 2.0 eV to a maximum of 4.0 eV is used, and an n-type organic semiconductor material having a LUMO energy level of 2.5 eV to 3.5 eV is more preferably used. For example, as a material for the electron transport layer of an organic EL element, any of the following conventionally known materials can be used, and among these, a material that satisfies the above-mentioned LUMO energy level requirements is preferred.
[0190] As the second material, specifically, there can be mentioned phosphine oxide derivatives such as phenyldipyrenephosphine oxide (POPy2), tris-1,3,5-(3'-(pyridin-3"-yl)phenyl)benzene (TmPhPyB), 1,3,5-tris(6-(3-(pyridin-3-yl)phenyl)pyridin-2-yl)benzene, pyridine derivatives such as 8,9-diphenyl-7,10-(3-(pyridin-3-yl))fluoranthene, quinoline derivatives such as (2-(3-(9-carbazolyl)phenyl)quinoline (mCQ)), 2-phenyl-4,6-bis(3,5-bipyridylphenyl)pyrimidine (BPyPPM), 2-methyl-4,6-bis(3,5-bipyridylphenyl)pyrimidine, 9-(4-(4,6 pyrimidine derivatives such as pyrimidine-2-yl)phenyl)-9H-carbazole, pyrazine derivatives, bathophenanthroline (BPhen), phenanthroline derivatives such as 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP), 2,4-bis(4-biphenyl)-6-(4'-(2-pyridyl)-4-biphenyl)-[1,3,5]triazine (MPT), tris-1,3,5-(3'-(pyridin-3″-yl)phenyl)triazine (TmPhPyTz), tris-1,3,5-([1,1′-biphenyl]-3-yl)triazine, 2-(3-(4,6-di(pyridin-3-yl)-1,3,5-triazine-2-yl)phenyl)-1-phenyl-1H-benzo[d ] imidazole, 9-(4-(4,6-diphenyl-1,3,5-triazin-2-yl)phenyl)-9H-3,9'-bicarbazole, 9-(4-(4,6-diphenyl-1,3,5-triazin-2-yl)phenyl)-9H-carbazole, 11-(4,6-diphenyl-1,3,5-triazin-2-yl)-12-phenyl-11,12-dihydroindole[2,3-a]carbazole, 12-(2-(4,6-diphenyl-1,3,5-triazin-2-yl)phenyl)-12H-benzofurano[2,3,a]carbazole, triazine derivatives such as 9-((4-(4,6-bipyridin-3-yl)-1,3,5-triazin-2-yl)phenyl)-9H-carbazole, 3-phenyl-4 triazole derivatives such as -(1'-naphthyl)-5-phenyl-1,2,4-triazole (TAZ), oxazole derivatives, oxadiazole derivatives such as 2-(4-biphenyl)-5-(4-tert-butylphenyl-1,3,4-oxadiazole) (PBD), imidazole derivatives such as 2,2',2"-(1,3,5-benzenetriyl)-tris(1-phenyl-1-H-benzimidazole) (TPBI), aromatic ring carboxylic acid anhydrides such as naphthalene-1,4,5,8-tetracarboxylic dianhydride and 3,4,9,10-perylenetetracarboxylic dianhydride, aromatic ring imide compounds such as N,N'-dimethyl-3,4,9,10-perylenetetracarboxylic acid diimide, isoindigo derivatives, 2,5-dihydropyrrolo[3,4-c]pyrrole-1,4-diketone derivatives (diketopyrrolopyrroles), compounds having a carbonyl group such as trimerized indenone, 1,2,5-thiadiazole derivatives such as naphtho[1,2-c:5,6-c']bis[1,2,5]thiadiazole and benzo[c][1,2,5]thiadiazole, compounds having a heterocyclic ring containing a carbonyl group such as the compound represented by the formula (30) described later, various metal complexes represented by bis[2-(2-hydroxyphenyl)benzothiazole]zinc (Zn(BTZ)2) and tris(8-hydroxyquinoline)aluminum (Alq3), 2,5-bis(6'-(2' , 2"-bipyridine))-1,1-dimethyl-3,4-diphenylthiole (PyPySPyPy) and other thiole derivatives represented by organic silane derivatives, tris(2,4,6-trimethyl-3-(pyridin-3-yl)phenyl)borane (3TPYMB), Japanese Patent Application No. 2012-228460, Japanese Patent Application No. 2015-503053, Japanese Patent Application No. 2015-053872, Japanese Patent Application No. 2015-081108 and Japanese Patent Application No. 2015-081109, etc., one or two or more of them can be used.,
[0191] In addition, the material of the light-emitting layer described later can also be used as the second material.
[0192] Among these second materials, it is more preferable to use phosphine oxide derivatives such as POPy2, boron-containing compounds such as compounds represented by the following formulas (6) to (9), metal complexes such as Alq3, pyridine derivatives such as TmPhPyB, and triazine derivatives such as TmPhPyTz. Among these second materials, it is particularly preferable that the second material is a boron-containing compound or a triazine derivative. It should be noted that n in formula (8) 1 Indicates an integer greater than 1.
[0193] [Chemistry 14]
[0194]
[0195] When a boron-containing compound is used as the second material having electron transport properties, a uniform organic thin film can be easily obtained by applying a coating composition comprising the first material and the second material. Such a coating composition comprising the electron-donating first material represented by the general formula (1) and the electron-transmitting second material is also one of the present invention. In addition, a coating composition comprising the electron-donating first material represented by the general formula (1) and not comprising the second material is also useful. Such a coating composition comprising the electron-donating first material represented by the general formula (1) is also one of the present invention.
[0196] In addition, boron-containing compounds and triazine derivatives have deep lowest unoccupied molecular orbitals (LUMO) and are therefore suitable as materials for electron injection layers of organic EL devices. Therefore, an organic thin film containing a boron-containing compound as the second material is particularly suitable as an electron injection layer of an organic EL device.
[0197] The ratio of the first material to the second material contained in the organic film of the present invention is not particularly limited and can be appropriately determined according to the types of compounds used in the first material and the second material, respectively. The ratio of the first material to the second material is preferably 0.1:99.9 to 20:1 in terms of mass ratio (first material: second material). More preferably, it is 0.5:99.5 to 10:1. In the case of the above ratio, the effect of improving the electron transport and electron injection properties brought about by including the first material and the second material in the organic film becomes significant.
[0198] The organic thin film in the present invention may be a single-layer film containing the first material and the second material, or a laminated film of a film containing at least the first material and a film containing at least the second material. In the case of a laminated film, it may be a laminated film of a film containing only the first material and a film containing only the second material, or a laminated film of a film containing the first material and the second material and a film containing only one of the first material and the second material. In the case of a laminated film of a film containing the first material and the second material and a film containing only one of the first material and the second material, the film containing only one of the first material and the second material may contain either the first material or the second material, but preferably contains the second material.
[0199] In addition, when such an organic thin film is used as a layer constituting an organic electroluminescent element, either a film comprising the first material and the second material or a film comprising only either the first material or the second material can be located on the cathode side, but it is preferred that the film comprising only either the first material or the second material is located on the cathode side.
[0200] When the organic thin film in the present invention is a laminated film of a film containing a first material and a second material and a film containing only the first material, both laminated films contain the first material, and the first materials contained in the two films may be the same or different.
[0201] Similarly, when the organic thin film in the present invention is a laminated film of a film containing a first material and a second material and a film containing only the second material, both laminated films contain the second material, and the second materials contained in the two films may be the same or different.
[0202] The organic film in the present invention only needs to contain at least the first material and the second material, and may contain other components, but the total ratio of the first material and the second material relative to the entire organic film is preferably higher than 95% by mass, more preferably higher than 99% by mass, and most preferably 100% by mass, that is, the organic film is composed only of the first material and the second material.
[0203] In addition, the method in which the organic film in the present invention includes a metal oxide is one of the preferred embodiments of the present invention. The organic electroluminescent element of the present invention may sometimes include a metal oxide layer. In addition, as described later, it has been reported that in the case of forming a metal film on an organic film and in any case of forming an organic film on a cathode, the metal diffuses a distance of several nanometers to the organic film side, so in the case of the organic electroluminescent element of the present invention using a metal oxide as a material for a cathode or a metal oxide layer, and forming the organic film of the present invention adjacent to the layer of the metal oxide, the organic film includes a metal oxide. In this way, the method in which the organic film includes a metal oxide is one of the preferred embodiments of the present invention.
[0204] The first material can exhibit excellent electron injection properties even when used alone. Such an organic thin film containing the first material but not the second material is also one of the present invention.
[0205] Therefore, an organic film that at least contains the first material is the organic film of the present invention, and a method in which the organic film further contains the second material to become a single-layer film containing the first material and the second material, or a laminated film of a film containing the first material and a film containing the second material can also be said to be one of the preferred embodiments of the organic film of the present invention.
[0206] In the organic thin film of the present invention including the first material and excluding the second material, the proportion of the first material relative to the entire organic thin film is preferably higher than 95% by mass, more preferably higher than 99% by mass, and most preferably 100% by mass, i.e., the organic thin film is composed only of the first material.
[0207] The following describes a method for manufacturing an organic thin film which is a single-layer film comprising a first material and a second material, or a laminated film comprising a film comprising the first material and a film comprising the second material. However, the manufacturing method, raw materials, etc. of an organic thin film which only comprises the first material and does not comprise the second material are the same, except that the second material is not included.
[0208] "Method for producing organic thin film"
[0209] Next, the method for producing the organic thin film of the present invention will be described with reference to examples.
[0210] The organic thin film of the present invention comprises a first material composed of an electron-donating compound having a structure represented by the above general formula (1) and a second material that transports electrons. Since the molecular weights of the first material and the second material are both relatively large, the organic thin film of the present invention can be formed not only by coating but also by evaporation. Therefore, there are few process constraints when manufacturing an organic EL element comprising the organic thin film of the present invention, and it is easy to use as a material for a layer constituting an organic EL element.
[0211] When an organic thin film is manufactured by vapor deposition, the same method as that used to manufacture other layers constituting an organic EL element by vapor deposition can be used, and the first material and the second material can be vapor deposited simultaneously or sequentially. When vapor deposition is performed sequentially, either the first material or the second material can be vapor deposited first. In addition, either one can be vapor deposited first and then both can be co-deposited, or both can be co-deposited and then either one can be vapor deposited. Such a method for manufacturing an organic thin film, which includes the step of simultaneously vapor depositing the first material, which is a compound having a structure represented by the above-mentioned general formula (1), and the second material for transporting electrons, on the formed surface of the organic thin film, is one of the preferred embodiments of the method for manufacturing an organic thin film of the present invention. In addition, the following method for manufacturing an organic thin film is also one of the preferred embodiments of the method for manufacturing an organic thin film of the present invention: a method for manufacturing an organic thin film comprising the step of first vapor-depositing either the first material or the second material on the surface to be formed of the organic thin film, and then vapor-depositing another material or two materials; or a method for manufacturing an organic thin film comprising the step of simultaneously vapor-depositing the first material and the second material on the surface to be formed of the organic thin film, and then vapor-depositing either the first material or the second material on the surface to be formed of the organic thin film.
[0212] In addition, the organic thin film of the present invention can also be manufactured by coating. In this case, a coating composition containing the first material and the second material for transmitting electrons can be prepared and the coating composition can be applied; or a coating composition containing the first material and a coating composition containing the second material can be prepared separately and they can be applied in sequence to manufacture the organic thin film. In the case of sequential coating, either the coating composition containing the first material or the coating composition containing the second material can be applied first. In addition, after coating a coating composition containing only one material, a coating composition containing both materials can be applied; or after coating a coating composition containing both materials, a coating composition containing only one material can be applied. Such a method for manufacturing an organic thin film, which includes the step of coating a coating composition containing the first material, which is a compound having a structure represented by the above-mentioned general formula (1), and the second material for transmitting electrons, on the surface to be formed of the organic thin film, is one of the preferred embodiments of the method for manufacturing an organic thin film of the present invention. In addition, the following method for manufacturing an organic thin film is also one of the preferred embodiments of the method for manufacturing an organic thin film of the present invention: a method for manufacturing an organic thin film comprising the step of first coating a coating composition containing only a first material or a coating composition containing only a second material on a formed surface of the organic thin film, and the step of coating a coating composition containing another material or two materials on a coating film formed by the step; or a method for manufacturing an organic thin film comprising the step of coating a coating composition containing both a first material and a second material, and the step of coating a coating composition containing only a first material or a second material on a coating film formed by the step.
[0213] Hereinafter, a method for producing an organic thin film by preparing a coating composition containing a first material composed of a compound having a structure represented by the general formula (1) and a second material that transports electrons and applying the coating composition will be described.
[0214] The coating composition can be obtained, for example, by supplying specific amounts of the first material and the second material to a solvent placed in a container and stirring to dissolve the materials.
[0215] As the solvent for dissolving the first material and the second material, for example, an inorganic solvent, an organic solvent, or a mixed solvent containing these can be used.
[0216] Examples of the inorganic solvent include nitric acid, sulfuric acid, ammonia, hydrogen peroxide, water, carbon disulfide, carbon tetrachloride, and ethylene carbonate.
[0217] Examples of the organic solvent include methyl ethyl ketone (MEK), acetone, diethyl ketone, methyl isobutyl ketone (MIBK), methyl isopropyl ketone (MIPK), diisobutyl ketone, 3,5,5-trimethylcyclohexanone, diacetone alcohol, cyclopentanone, cyclohexanone and other ketone solvents; methanol, ethanol, isopropyl alcohol, ethylene glycol, diethylene glycol (DEG), glycerol and other alcohol solvents; diethyl ether, diisopropyl ether, 1,2-dimethoxyethane (DME), 1,4-dioxane, tetrahydrofuran (THF), tetrahydropyran (THP), anisole, diethylene glycol dimethyl ether (diglyme), diethylene glycol ethyl ether (carbitol) and other ether solvents; methyl cellosolve, ethyl cellosolve, phenyl cellosolve and other cellosolve solvents; hexane, pentane, heptane, heptane, cyclohexane and other aliphatic hydrocarbon solvents; toluene, xylene, benzene and other aromatic hydrocarbon solvents. , aromatic heterocyclic compound solvents such as pyridine, pyrazine, furan, pyrrole, thiophene, methylpyrrolidone, etc., amide solvents such as N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMA), halogenated solvents such as chlorobenzene, dichloromethane, chloroform, 1,2-dichloroethane, ester solvents such as ethyl acetate, methyl acetate, ethyl formate, dimethyl sulfoxide (DMSO), sulfolane, etc., nitrile solvents such as acetonitrile, propionitrile, acrylonitrile, organic acid solvents such as formic acid, acetic acid, trichloroacetic acid, trifluoroacetic acid, etc., and the like, among which ketone solvents such as methyl ethyl ketone (MEK), acetone, diethyl ketone, methyl isobutyl ketone (MIBK), methyl isopropyl ketone (MIPK), diisobutyl ketone, 3,5,5-trimethylcyclohexanone, diacetone alcohol, cyclopentanone, etc. are preferred.
[0218] As a method for applying a coating composition containing the first material and the second material, various coating methods can be used, for example, spin coating, cast coating, micro-gravure coating, gravure coating, rod coating, roller coating, wire bar coating, dip coating, spraying, screen printing, flexographic printing, offset printing, inkjet printing and the like.
[0219] After the coating composition is applied in this way, an annealing treatment is preferably performed. The annealing treatment is preferably performed at 70 to 200° C. for 0.1 to 5 hours in a nitrogen atmosphere or in the air. By performing such an annealing treatment, the solvent can be vaporized to form an organic thin film.
[0220] In addition, an organic thin film containing the electron-donating first material represented by the general formula (1) and not containing the second material is also useful as a material for an organic EL element, etc. A method for manufacturing an organic thin film including a step of forming a film containing the electron-donating first material represented by the general formula (1) on a formed surface is also one of the present inventions, and a method including a step of forming a film containing the electron-donating first material represented by the general formula (1) on a formed surface containing the second material is one of the preferred embodiments of the method for manufacturing the organic thin film.
[0221] "Organic EL elements"
[0222] The present invention also relates to an organic electroluminescent (EL) element having a light-emitting layer between a cathode and an anode, and further comprising any one of a layer of the organic thin film of the present invention, a layer of a laminated film of the organic thin film layer and a metal oxide layer, or a layer comprising a material for an organic electroluminescent element of the present invention.
[0223] The above-mentioned organic thin film layer, the layer of the laminated film of the organic thin film layer and the metal oxide layer, and the layer containing the material for the organic electroluminescent element of the present invention can be located between the cathode and the light-emitting layer, or between the anode and the light-emitting layer in the organic EL element of the present invention, but is preferably located between the cathode and the light-emitting layer.
[0224] The layer containing the material for an organic electroluminescent device of the present invention may contain any other components as long as it contains the compound having the structure represented by the general formula (1). However, it is preferably a layer consisting only of the compound having the structure represented by the general formula (1).
[0225] The present invention also relates to an organic electroluminescent (EL) element, which is an organic electroluminescent (EL) element having a light-emitting layer between a cathode and an anode, wherein the organic thin film layer of the present invention or a layer of a laminated film of the organic thin film layer and a metal oxide layer is included between the cathode and the anode, and the light-emitting layer contains a second material. The present invention also relates to an organic electroluminescent (EL) element, which is an organic thin film layer of the present invention or a layer of a laminated film of the organic thin film layer and a metal oxide layer between the cathode and the anode, wherein the organic thin film or the laminated film is adjacent to the light-emitting layer and contains a material used as a second material in the light-emitting layer, or a film containing the second material in the organic thin film or the laminated film is the light-emitting layer.
[0226] The compound represented by the general formula (1) as the first material of the present invention has very excellent electron injection properties, so it can directly inject electrons even into the luminescent material or host material used in the luminescent layer. Therefore, by using the first material of the present invention in the electron injection layer, the number of materials used and the number of layers to be stacked can be reduced, thereby making an organic EL element with a simpler structure.
[0227] That is, when the element using the organic thin film or laminated film of the present invention is made into a layer containing the first material, a layer containing the second material and an element adjacent to the light-emitting layer and the light-emitting material or the main material used in the light-emitting layer is used as the material of the layer containing the second material, electrons can also be injected from the layer containing the first material, thereby, the layer containing the second material and the light-emitting layer can be formed using a common material, so the number of materials used can be reduced. In this case, the second material can be any one of the light-emitting material and the main material of the light-emitting layer. In addition, when the light-emitting material or the main material of the light-emitting layer is used to form a layer containing the second material and used as a light-emitting layer, it is not necessary to set the light-emitting layer separately, so the number of layers stacked can be reduced and an organic EL element with a simpler structure can be made. In addition, if the second material is used as the material of the layer adjacent to the anode side of the light-emitting layer, the number of layers stacked can be further reduced and an organic EL element with a simpler structure can be made. Therefore, the light-emitting layer includes the second material, or the mode of having a layer containing the above-mentioned second material between the anode and the above-mentioned light-emitting layer is one of the preferred embodiments of the organic electroluminescent (EL) element of the present invention.
[0228] Next, the organic EL device of the present invention will be described in detail with reference to examples.
[0229] Figure 4 This is a schematic cross-sectional view for explaining an example of the organic EL element of the present invention. Figure 4 The organic EL element 1 of the present embodiment shown includes a light-emitting layer 6 between a cathode 3 and an anode 9 . Figure 4 In the organic EL element 1 shown, an electron injection layer 5 composed of the organic thin film of the present invention or the material for an organic electroluminescent element of the present invention is provided between the cathode 3 and the light-emitting layer 6. In addition, an oxide layer 4 is provided between the cathode 3 and the electron injection layer 5 composed of the organic thin film of the present invention or the material for an organic electroluminescent element of the present invention, and the oxide layer 4 is adjacent to the electron injection layer 5. These are all preferred embodiments of the organic EL element of the present invention.
[0230] The organic EL element 1 of the present embodiment has a laminated structure in which a cathode 3, an inorganic oxide layer 4, an electron injection layer 5, an electron transport layer 10, a light-emitting layer 6, a hole transport layer 7, a hole injection layer 8, and an anode 9 are sequentially formed on a substrate 2. Such a mode in which an inorganic oxide layer is provided between the cathode and the layer of the organic thin film or the layer of the material for the organic electroluminescent element of the present invention is one of the preferred embodiments of the organic EL element of the present invention.
[0231] Figure 4 The organic EL element 1 shown is an organic EL element of an inverted structure in which a cathode 3 is arranged between a substrate 2 and a light-emitting layer 6. Figure 4The organic EL element 1 shown is an organic-inorganic hybrid organic electroluminescent element (HOILED element) in which a part of the layers constituting the organic EL element (at least the inorganic oxide layer 4 ) is formed using an inorganic compound.
[0232] Figure 4 The organic EL element 1 shown may be a top emission type element in which light is extracted on the side opposite to the substrate 2 , or may be a bottom emission type element in which light is extracted on the substrate 2 side.
[0233] Figure 5 This is a diagram showing an example of the element configuration in the case where the organic EL element of the present invention is an organic EL element of a forward structure in which the light-emitting layer 6 is disposed between the substrate 2 and the cathode 3 .
[0234] As described above, the compound represented by the general formula (1) of the present invention has very excellent electron injection properties, and thus can directly inject electrons into the material used in the light-emitting layer. Therefore, when using an organic EL element material containing the compound represented by the general formula (1) of the present invention, even in the case of, for example, Figure 6 In the case of an organic EL element with a simple structure in which the electron transport layer 10 is formed using the material used in the light-emitting layer, and the light-emitting layer 6 and the electron transport layer 10 are made of the same material, it is possible to operate at a low driving voltage by using a compound represented by the general formula (1) in the electron injection layer 5. In this case, at least one material used can be reduced compared to a typical organic EL element. Here, if the electron transport layer 10 contains the second material of the present invention, it can also be said that the organic EL element uses the organic thin film of the present invention.
[0235] Furthermore, since holes can be injected relatively easily from the hole injection layer 8 into the material used in the light-emitting layer, when the material for an organic EL device containing the compound represented by the general formula (1) of the present invention is used for the electron injection layer 5, even if Figure 7 As shown, the material used in the light-emitting layer is used for the hole transport layer 7, and it can also operate at a low driving voltage. In this case, at least two materials used can be reduced compared to a typical organic EL element. Here, if the electron transport layer 10 contains the second material of the present invention, it can also be said that the organic EL element uses the organic thin film of the present invention.
[0236] It should be noted that although the diagram of the organic EL device with a forward structure is used for the description here, the organic EL device in which the light-emitting layer of the present invention includes the second material is not limited to the forward structure, and may also have a reverse structure.
[0237] In the following present embodiment, an organic EL element with a reverse structure is cited as an example for explanation, but the organic EL element of the present invention may also be an element with a forward structure in which an anode is arranged between a substrate and a light-emitting layer. When the organic EL element of the present invention is a forward structure, it also has the above-mentioned organic thin film between a cathode and a light-emitting layer as in the case of a reverse structure. In addition, in the case of a reverse structure, the electron injection layer is sometimes also referred to as an organic buffer layer. The materials, thicknesses and sealing of each layer constituting the organic EL element 1 described below, except for the materials of the cathode and anode described later, are the same for the organic EL element with a forward structure. All of the contents described below can also be applied to an organic EL element with a forward structure.
[0238] "Substrate"
[0239] Examples of the material of the substrate 2 include resin materials and glass materials.
[0240] Examples of the resin material used for the substrate 2 include polyethylene terephthalate, polyethylene naphthalate, polypropylene, cycloolefin polymer, polyamide, polyethersulfone, polymethyl methacrylate, polycarbonate, polyarylate, etc. When a resin material is used as the material for the substrate 2, an organic EL element 1 having excellent flexibility can be obtained, which is preferred.
[0241] Examples of the glass material used for the substrate 2 include quartz glass and soda glass.
[0242] When the organic EL element 1 is a bottom emission type element, a transparent substrate is used as a material of the substrate 2 .
[0243] When the organic EL element 1 is a top-emitting element, not only a transparent substrate but also an opaque substrate can be used as the material of the substrate 2. Examples of the opaque substrate include a substrate made of a ceramic material such as alumina, a substrate having an oxide film (insulating film) formed on the surface of a metal plate such as stainless steel, and a substrate made of a resin material.
[0244] The average thickness of the substrate 2 can be determined according to the material of the substrate 2, and is preferably 0.1 to 30 mm, and more preferably 0.1 to 10 mm. The average thickness of the substrate 2 can be measured using a digital multimeter or a vernier caliper.
[0245] "cathode"
[0246] The cathode 3 is formed on the substrate 2 in direct contact.
[0247] As the material of the cathode 3, ITO (indium tin oxide), IZO (indium zinc oxide), FTO (fluorine tin oxide), In3O3, SnO2, SnO2 containing Sb, ZnO containing Al and other oxides, Al, Au, Pt, Ag, Cu or conductive materials containing alloys thereof can be cited. Among them, ITO, IZO, FTO and Al are preferably used as the material of the cathode 3.
[0248] The average thickness of the cathode 3 is not particularly limited, but is preferably 10 to 500 nm, more preferably 100 to 200 nm.
[0249] The average thickness of the cathode 3 can be measured using a probe profilometer or a spectroscopic ellipsometer.
[0250] When the organic EL device of the present invention is a forward structure device in which an anode is arranged between the substrate and the light-emitting layer, these materials can be used as the material of the anode. In this case, the average thickness of the anode is preferably the same as that of the cathode 3 described above.
[0251] "Oxide layer"
[0252] The inorganic oxide layer 4 has a function as an electron injection layer and / or a function as a cathode.
[0253] The oxide layer 4 is a layer of semiconductor or insulator laminated thin films. Specifically, the oxide layer 4 may be a layer composed of a single metal oxide; a layer in which a layer in which two or more metal oxides are mixed and a layer in which a single metal oxide is laminated, or both; or any of a layer in which two or more metal oxides are mixed.
[0254] Examples of the metal element constituting the metal oxide forming the oxide layer 4 include magnesium, calcium, strontium, barium, titanium, zirconium, hafnium, vanadium, niobium, tantalum, chromium, molybdenum, tungsten, manganese, indium, gallium, iron, cobalt, nickel, copper, zinc, cadmium, aluminum, and silicon.
[0255] When oxide layer 4 includes a layer in which two or more metal oxides are mixed, it is preferably a layer in which at least one of the metal elements constituting the metal oxides is composed of magnesium, aluminum, calcium, zirconium, hafnium, silicon, titanium, or zinc.
[0256] When the oxide layer 4 is a layer composed of a single metal oxide, it is preferably a layer composed of a metal oxide selected from the group consisting of magnesium oxide, aluminum oxide, zirconium oxide, hafnium oxide, silicon oxide, titanium oxide, and zinc oxide.
[0257] In the case where the oxide layer 4 is a layer in which a layer in which two or more metal oxides are mixed and one or both of a layer consisting of a single metal oxide are stacked, or a layer in which two or more metal oxides are mixed, examples include a layer in which a combination of two metal oxides selected from titanium oxide / zinc oxide, titanium oxide / magnesium oxide, titanium oxide / zirconium oxide, titanium oxide / aluminum oxide, titanium oxide / hafnium oxide, titanium oxide / silicon oxide, zinc oxide / magnesium oxide, zinc oxide / zirconium oxide, zinc oxide / hafnium oxide, zinc oxide / silicon oxide, and calcium oxide / aluminum oxide are stacked and / or mixed; a layer in which a combination of three metal oxides selected from titanium oxide / zinc oxide / magnesium oxide, titanium oxide / zirconium oxide, titanium oxide / zinc oxide / aluminum oxide, titanium oxide / zinc oxide / hafnium oxide, titanium oxide / zinc oxide / silicon oxide, and indium oxide / gallium oxide / zinc oxide are stacked and / or mixed, etc.
[0258] The oxide layer 4 may include an oxide semiconductor IGZO (indium gallium zinc oxide) and / or an electronic compound 12CaO·7Al 2 O 3 which exhibit excellent characteristics as a special composition.
[0259] The average thickness of the oxide layer 4 is not particularly limited, but is preferably 1 to 1000 nm, more preferably 2 to 100 nm.
[0260] The average thickness of oxide layer 4 can be measured using a probe profilometer or a spectroscopic ellipsometer.
[0261] "Electron injection layer"
[0262] The electron injection layer 5 improves the injection speed and electron transport properties of electrons from the cathode to the light emitting layer 6. The electron injection layer 5 is composed of the above-mentioned organic thin film.
[0263] The average thickness of the electron injection layer 5 is preferably 0.5 to 100 nm, more preferably 1 to 100 nm, further preferably 5 to 100 nm, and particularly preferably 10 to 50 nm. When the average thickness of the electron injection layer 5 is 0.5 nm or more, the electron injection layer 5 can be formed by using any of the methods of applying a coating composition comprising the first material and the second material, and sequentially applying a coating composition comprising the first material and a coating composition comprising the second material, so that a smooth surface electron injection layer 5 can be obtained. Alternatively, the electron injection layer 5 composed of the first material and the second material can be obtained by co-deposition using a vacuum evaporation method. In addition, when the average thickness of the electron injection layer 5 is 100 nm or less, the increase in the driving voltage of the organic EL element 1 caused by the provision of the electron injection layer 5 can be fully suppressed.
[0264] It should be noted that, when forming a film including the first material and the second material, it can be Figures 8-1 to 14-1 (In the case of the forward structure, Figures 8-2 to 14-2 ) shown in any structure. For example, it can be composed of a single film, and the film as a whole constitutes an electron injection layer ( Figure 8-1 , 8-2 ); It is also possible to form a film consisting of only the first material or only the second material adjacent to the cathode or the oxide, and to form the other adjacent to the film ( Figure 9-1 , 9-2 , Figure 10-1 , 10-2 ). Alternatively, a film including the first material and the second material may be formed adjacent to the cathode or the oxide, and a film consisting only of the second material may be formed adjacent to the film ( Figure 11-1 , 12-2 ); a film not containing the first material but consisting only of the second material may be formed adjacent to the cathode or the oxide, and a film containing the first material and the second material may be formed adjacent to the film ( Figure 12-1 , 12-2 ). In addition, the film may be formed in a manner such that the following structure is formed: a three-layer film having a film composed only of the first material or a film containing the first material and the second material sandwiched between films composed only of the second material ( Figure 13-1 , 13-2 , Figure 14-1 , 14-2 ).
[0265] Figures 8-1 to 14-1 , Figures 8-2 to 14-2 Any film of the structure shown in is included in the present invention. Figures 11-1 to 14-1 , Figures 11-2 to 14-2 When the second material is contained in two adjacent films or two or more films in the three-layer structure film as shown, the second materials contained in the two or more films may be the same or different.
[0266] In addition, in these structures, for a layer including only the first material Figure 9-1 , 9-2 , Figure 10-1 , 10-2 as well as Figure 13-1 , 13-2 , the layer composed only of the first material can be regarded as a layer formed by the organic thin film of the present invention (the organic thin film containing only the first material and not the second material).
[0267] The average thickness of the electron injection layer 5 can be measured using, for example, a probe profilometer or a spectroscopic ellipsometer.
[0268] As described above, the first material as an electron-donating organic material is a material capable of causing other materials to generate negative charges. Therefore, in order to fully perform electron injection from the cathode 3 or the oxide layer 4, it is preferred that the first material exists more on the cathode 3 or the oxide layer 4 side. However, even if the negative charge is not in direct contact with the oxide or the cathode, it can contribute to the promotion of electron injection. Therefore, even if Figure 9-1 , 9-2 , Figure 12-1 , 12-2 , Figure 13-1 , 13-2 , Figure 14-1 , 14-2 Even in such a layered structure, the electron injection effect due to the presence of the first material can be obtained.
[0269] It is reported that in either the case of metal deposition on an organic film or the case of organic film deposition on a cathode, the metal diffuses to the organic film side by a distance of several nanometers (see Lee, JH, Yi, Y. & Moon, DW Direct evidence of Al diffusion into tris-(8-hydroquinoline)aluminum layer: medium energy ion scattering analysis. Applied Physics Letters 93, doi: 10.1063 / 1.3002290 (2008) and non-patent document 12). Therefore, even in a laminated structure where the second material exists on the cathode 3 side, the electron injection effect due to the coordination reaction with the first material can be obtained by the diffusion of the metal. That is, even if the first material is not directly formed on the cathode 3 or the oxide layer 4, the effect of the present invention can be obtained.
[0270] As described above, the first material as an electron-donating organic material is a material having the ability to cause other materials to generate negative charges. From the perspective of fully exerting the effect of the organic thin film of the present invention, the organic thin film of the present invention preferably forms a layer containing the first material adjacent to the cathode or the oxide layer ( Figure 8-1 , 8-2 , Figure 10-1 , 10-2 , Figure 11-1 , 11-2 ), but even if Figure 9-1 , 9-2 , Figure 12-1 , 12-2 , Figure 13-1 , 13-2 , Figure 14-1 , 14-2The effect can also be obtained by directly forming a layer containing the first material without being adjacent to the cathode or the oxide layer as shown. Any laminated film thus obtained, i.e., a laminated film consisting of an oxide layer and a layer of the organic thin film of the present invention formed adjacent to the oxide layer, and a laminated film consisting of a cathode and a layer of the organic thin film of the present invention formed adjacent to the cathode, is also one of the present invention.
[0271] When the organic EL element includes an oxide layer and a layer of the organic thin film of the present invention formed adjacent to the oxide layer in a laminated structure, or when the organic EL element includes a cathode and a layer of the organic thin film of the present invention formed adjacent to the cathode in a laminated structure, the organic EL element can be said to be composed of the laminated film of the present invention. Such an organic EL element composed of the laminated film of the present invention is also one of the present invention.
[0272] In the organic EL device of the present invention, the electron injection layer may have Figure 11-1 , 11-2 , Figure 12-1 , 12-2 or Figure 14-1 , 14-2 Such a laminated film. That is, an aspect in which a laminated film including a film including the first material and the second material and a film including the second material is provided between the cathode and the light-emitting layer is one of the preferred embodiments of the organic EL device of the present invention.
[0273] In this case, an organic EL element having a layer containing the second material between the light-emitting layer and the film containing the first material and the second material, and an organic EL element having a layer containing the second material between the cathode and the film containing the first material and the second material are both preferred embodiments of the organic EL element of the present invention.
[0274] "Electron Transport Materials"
[0275] As the electron transport layer 10 , any material that can be generally used as a material for an electron transport layer can be used.
[0276] Specifically, as materials for the electron transport layer 10, there can be cited: phosphine oxide derivatives such as phenyldipyrenephosphine oxide (POPy2), pyridine derivatives such as tris-1,3,5-(3'-(pyridin-3''-yl)phenyl)benzene (TmPhPyB), quinoline derivatives such as (2-(3-(9-carbazolyl)phenyl)quinoline (mCQ)), pyrimidine derivatives such as 2-phenyl-4,6-bis(3,5-bipyridylphenyl)pyrimidine (BPyPPM), pyrazine derivatives, phenanthroline derivatives such as bathophenanthroline (BPhen), 2,4-bis(4-biphenyl)-6-(4'-(2-pyridinyl)phenyl)quinoline (BPhen), triazine derivatives such as 2-(4-biphenyl)-5-(4-tert-butylphenyl-1,3,4-oxadiazole) (PBD), imidazole derivatives such as 2,2',2"-(1,3,5-benzenetriyl)-tris(1-phenyl-1-H-benzimidazole) (TPBI), aromatic ring carboxylic acid anhydrides such as naphthalene-1,4,5,8-tetracarboxylic dianhydride and 3,4,9,10-perylenetetracarboxylic dianhydride, Aromatic imide compounds such as N,N'-dimethyl-3,4,9,10-perylenetetracarboxylic acid diimide, isoindigo derivatives, 2,5-dihydropyrrolo[3,4-c]pyrrole-1,4-dione derivatives (diketopyrrolopyrrole), compounds having a carbonyl group such as trimerone, 1,2,5-thiadiazole derivatives such as naphtho[1,2-c:5,6-c']bis[1,2,5]thiadiazole and benzo[c][1,2,5]thiadiazole, various metals represented by bis[2-(2-hydroxyphenyl)benzothiazole]zinc (Zn(BTZ)2), tris(8-hydroxyquinoline)aluminum (Alq3), etc. The invention may include boron-containing compounds described in Japanese Patent Application Nos. 2012-228460, 2015-503053, 2015-053872, 2015-081108 and 2015-081109, and one or more thereof may be used.
[0277] Among these materials for the electron transport layer 10 , it is particularly preferable to use a phosphine oxide derivative such as POPy2, a metal complex such as Alq3, or a pyridine derivative such as TmPhPyB.
[0278] It should be noted that, as in the above-mentioned organic EL element in which a layer containing a second material is formed using a light-emitting material or a main material used in the light-emitting layer, as long as the organic EL element can function, the organic EL element of the present invention may not have an electron transport layer using the above-mentioned electron transport material in the layered structure.
[0279] When the organic EL element of the present invention uses an organic thin film composed of only the first material as the electron injection layer, the second material of the organic thin film of the present invention can be used as the material of the electron transport layer 10 .
[0280] When the organic EL device of the present invention uses a single-layer film including the first material and the second material as the electron injection layer 5 , the electron transport layer 10 may not be included.
[0281] The average thickness of the electron transport layer 10 is not particularly limited, but is preferably 10 to 150 nm, and more preferably 20 to 100 nm.
[0282] The average thickness of the electron transport layer 10 can be measured using a probe profilometer or a spectroscopic ellipsometer.
[0283] "Luminous Layer"
[0284] As a material for forming the light-emitting layer 6, any material that can be generally used as a material for the light-emitting layer 6 can be used, or a mixture of these materials can be used. Specifically, for example, as the light-emitting layer 6, bis[2-(2-benzothiazolyl)phenol]zinc(II) (Zn(BTZ)2) and tris[1-phenylisoquinoline]iridium(III) (Ir(piq)3) can be included.
[0285] The material forming the light emitting layer 6 may be a low molecular compound or a high molecular compound. It should be noted that the low molecular material in the present invention refers to a material that is not a high molecular material (polymer), and does not necessarily refer to an organic compound with a low molecular weight.
[0286] Examples of the polymer material forming the light-emitting layer 6 include: polyacetylene compounds such as trans-polyacetylene, cis-polyacetylene, poly(diphenylvinylene) (PDPA), and poly(alkylphenylvinylene) (PAPA); poly(p-phenylenevinylene) (PPV), poly(2,5-dialkoxy-p-phenylenevinylene) (RO-PPV), cyano-substituted poly(p-phenylenevinylene) (CN-PPV), poly(2-dimethyloctylsilyl-p-phenylenevinylene) (DMOS-PPV), and poly(2-methoxy-5-(2'-ethylhexyloxy)-p-phenylenevinylene) (MEH-PPV); poly(3-alkylthiophene) (PAT), and poly(oxypropylene) triol (POPT); poly(9,9-dialkylfluorene) (PDAF), poly(dioctylfluorene-alt-benzothiadiazole) (F8BT), α,ω- -polyfluorene compounds such as bis[N,N'-di(methylphenyl)aminophenyl]-poly[9,9-bis(2-ethylhexyl)fluorene-2,7-diyl](PF2 / 6am4), poly(9,9-dioctyl-2,7-di-1,2-vinylenefluorenyl-alternating copolymer(anthracene-9,10-diyl); poly(p-phenylene) compounds such as poly(PPP) and poly(1,5-dialkoxyp-phenylene) (RO-PPP); poly(N-vinylcarbazole) compounds such as poly(PVK); polysilane compounds such as poly(methylphenylsilane) (PMPS), poly(naphthylphenylsilane) (PNPS), and poly(biphenylphenylsilane) (PBPS); and boron compound-based polymer materials described in Japanese Patent Application No. 2010-230995 and Japanese Patent Application No. 2011-6457, etc.
[0287] Examples of the low molecular weight material for forming the light emitting layer 6 include a tricoordinate iridium complex having 2,2'-bipyridine-4,4'-dicarboxylic acid as a ligand, fac-tris(2-phenylpyridine)iridium (Ir(ppy)3), fac-tris(3-methyl-2-phenylpyridine-N,C2'-)iridium(III) (Ir(mppy)3), 8-hydroxyquinoline aluminum (Alq3), tris(4-methyl-8-hydroxyquinoline)aluminum(III) (Almq3), 8-hydroxyquinoline zinc (Znq2 ), various metal complexes such as (1,10-phenanthroline)-tris(4,4,4-trifluoro-1-(2-thienyl)-butane-1,3-dione) europium(III) (Eu(TTA)3(phen)), 2,3,7,8,12,13,17,18-octaethyl-21H,23H-porphineplatinum(II); benzene compounds such as distyrylbenzene (DSB) and diaminodistyrylbenzene (DADSB); naphthalene compounds such as naphthalene and Nile red; phenanthrene compounds such as phenanthrene; 6-Nitro Such perylene compounds; perylene compounds such as perylene and N,N'-bis(2,5-di-tert-butylphenyl)-3,4,9,10-perylene-dicarboxylic acid imide (BPPC); coronet compounds such as coronet; anthracene compounds such as anthracene, bis-vinyl anthracene, and (9,10-bis(4-(9H carbazole-9-yl)-2,6-dimethylphenyl))-9,10-diboranthracene (CzDBA) represented by formula (31) described later; pyrene compounds such as pyrene; 4-(dicyanomethylene)-2-methyl-6-(p-dimethylamino)- Pyran compounds such as stilbene (2,5-dibenzoxazolidinyl)-4H-pyran (DCM); acridine compounds such as acridine; stilbene compounds such as thiophene; benzoxazole compounds such as benzoxazole; benzimidazole compounds such as benzimidazole; benzothiazole compounds such as 2,2'-(p-phenylenedivinylene)bisbenzothiazole; butadiene compounds such as distyryl (1,4-diphenyl-1,3-butadiene) and tetraphenylbutadiene Olefin compounds; naphthalene imide compounds such as naphthalene imide; coumarin compounds such as coumarin; perinone compounds such as perinone; oxadiazole compounds such as oxadiazole; aldazine compounds; cyclopentadiene compounds such as 1,2,3,4,5-pentaphenyl-1,3-cyclopentadiene (PPCP); quinacridone compounds such as quinacridone and quinacridone red; pyridine compounds such as pyrrolopyridine and thiadiazolopyridine; 2,4-diphenyl-6-diol represented by formula (26) described below Triazine compounds such as ((12-phenylindole)[2,3-a]carbazole-11-yl)-1,3,5-triazine (DIC-TRZ); spirocyclic compounds such as 2,2',7,7'-tetraphenyl-9,9'-spirobifluorene; metal or metal-free phthalocyanine compounds such as phthalocyanine (H2Pc) and copper phthalocyanine; and boron compound materials described in Japanese Patent Publication No. 2009-155325, Japanese Patent Publication No. 2011-184430 and Japanese Patent Application No. 2011-6458, etc.
[0288] Examples of the host material of the light-emitting layer include carbazole compounds such as 4,4′-bis(9H-carbazol-9-yl)biphenyl (CPB); silicon compounds; phenanthroline compounds; and triphenylene compounds.
[0289] The average thickness of the light-emitting layer 6 is not particularly limited, but is preferably 10 to 150 nm, more preferably 20 to 100 nm.
[0290] The average thickness of the light-emitting layer 6 can be measured using a probe profilometer, or can be measured using a quartz crystal thickness gauge when the light-emitting layer 6 is formed.
[0291] "Hole Transport Layer"
[0292] As the hole transporting organic material used in the hole transporting layer 7 , various p-type high molecular weight materials (organic polymers) and various p-type low molecular weight materials can be used alone or in combination.
[0293] Specifically, as the material of the hole transport layer 7, for example, N,N'-di(1-naphthyl)-N,N'-diphenyl-1,1'-biphenyl-4,4'-diamine (α-NPD), N4,N4'-bis(dibenzo[b,d]thiophene-4-yl)-N4,N4'-diphenylbiphenyl-4,4'-diamine (DBTPB), N3,N3'-bis(dibenzo[b,d]thiophene-4-yl)-N3 ,N3"'-diphenyl-[1,1':2',1":2",1"'-quadrenyl]-3,3"'-diamine (4DBTP3Q), polyaromatic amine, fluorene-aromatic amine copolymer, fluorene-bithiophene copolymer, poly(N-vinylcarbazole), polyvinylpyrene, polyvinylanthracene, polythiophene, polyalkylthiophene, polyhexylthiophene, poly(p-phenylene vinylene), poly(thiophene acetylene), pyrene formaldehyde resin, ethylcarbazole formaldehyde resin or its derivatives, etc. These materials for the hole transport layer 7 can also be used as a mixture with other compounds. As an example, as a mixture of polythiophene containing a material used as a hole transport layer 7, poly(3,4-ethylenedioxythiophene / styrenesulfonic acid) (PEDOT / PSS) and the like can be cited.
[0294] It should be noted that, as described above, since holes can be injected relatively easily from the hole injection layer into the material used in the light-emitting layer, even if the material used in the light-emitting layer is used for the hole transport layer, it can operate at a low driving voltage. Therefore, the organic EL element of the present invention may not have a hole transport layer using the above-mentioned hole transport material.
[0295] The average thickness of the hole transport layer 7 is not particularly limited, but is preferably 10 to 150 nm, more preferably 20 to 100 nm.
[0296] The average thickness of the hole transport layer 7 can be measured using, for example, a probe profilometer or a spectroscopic ellipsometer.
[0297] "Hole injection layer"
[0298] The hole injection layer 8 may be a layer composed of an inorganic material or a layer composed of an organic material. Inorganic materials are more stable than organic materials, and thus, higher resistance to oxygen and water is more likely to be obtained than when using organic materials.
[0299] There is no particular limitation on the inorganic material, and for example, one or more metal oxides such as vanadium oxide (V2O5), molybdenum oxide (MoO3), and ruthenium oxide (RuO2) can be used.
[0300] As organic materials, low molecular weight materials such as dipyrazino[2,3-f:2',3'-h]quinoxaline-2,3,6,7,10,11-hexacarbonitrile (HAT-CN), 2,3,5,6-tetrafluoro-7,7,8,8-tetracyanoquinodimethane (F4-TCNQ), fullerene, poly(3,4-ethylenedioxythiophene) / polystyrene sulfonate (ester) (PEDOT:PSS), etc. can be used.
[0301] The average thickness of the hole injection layer 8 is not particularly limited, but is preferably 1 to 1000 nm, more preferably 5 to 50 nm.
[0302] The average thickness of the hole injection layer 8 can be measured during film formation using a quartz crystal thickness gauge, a probe profilometer, or a spectroscopic ellipsometer.
[0303] "anode"
[0304] Examples of the material used for the anode 9 include ITO, IZO, Au, Pt, Ag, Cu, Al, and alloys containing these. Among them, ITO, IZO, Au, Ag, and Al are preferably used as the material for the anode 9.
[0305] The average thickness of the anode 9 is not particularly limited, but is preferably 10 to 1000 nm, more preferably 30 to 150 nm. In addition, even when a light-impermeable material is used as the material of the anode 9, for example, by making the average thickness about 10 to 30 nm, it can be used as a transparent anode in a top-emitting organic EL element.
[0306] The average thickness of the anode 9 can be measured using a quartz crystal thickness gauge when the anode 9 is formed.
[0307] When the organic EL device of the present invention is a forward structure device, the material obtained by adding Mg to these materials can be used as a cathode material. In this case, the average thickness of the cathode is preferably the same as that of the anode 9 described above.
[0308] "seal"
[0309] Figure 4 The organic EL element 1 shown may be sealed as necessary.
[0310] For example, Figure 4 The organic EL element 1 shown can be sealed by using a sealed container (not shown) having a concave space for accommodating the organic EL element 1 and an adhesive for bonding the edge of the sealed container to the substrate 2. Alternatively, the organic EL element 1 can be sealed by accommodating the sealed container and filling it with a sealing material composed of an ultraviolet (UV) curable resin or the like. In addition, for example, Figure 4 The organic EL element 1 shown can also be sealed using a sealing member composed of a plate member (not shown) arranged on the anode 9 and a frame member (not shown) arranged along the edge of the plate member on the side opposite to the anode 9, and an adhesive for bonding the plate member to the frame member and the frame member to the substrate 2.
[0311] When the organic EL element 1 is sealed using a sealed container or a sealing member, a desiccant material that absorbs moisture may be disposed inside the sealed container or inside the sealing member. In addition, a material that absorbs moisture may be used as the sealed container or the sealing member. In addition, a space may be formed inside the sealed container or inside the sealing member after sealing.
[0312] As will Figure 4 The material of the sealing container or sealing member used when the organic EL element 1 is sealed can be a resin material, a glass material, etc. The resin material and the glass material used in the sealing container or the sealing member can be the same as the material used in the substrate 2.
[0313] In the organic EL element 1 of the present embodiment, when the electron injection layer is formed using an organic thin film comprising a first material that is an electron-donating organic material represented by the above general formula (1) and a second material that is a boron-containing compound represented by the above general formula (6), excellent durability can be obtained compared to the case where an alkali metal that is unstable in the atmosphere is used as the electron injection layer. Therefore, if the water vapor permeability of the sealed container or the sealing member is 10 -4 ~10 -3 Order of magnitude (g / m 2 / day), the degradation of the organic EL element 1 can be sufficiently suppressed. Therefore, as the material of the sealed container or the sealing member, a material with a water vapor transmission rate of 10 -3 Order of magnitude (g / m 2 A resin material having a specific surface area of less than 100 nm / day) can realize an organic EL element 1 having excellent flexibility.
[0314] "Method for producing organic EL element"
[0315] Next, as an example of a method for producing an organic EL element of the present invention, Figure 4 A method for manufacturing the organic EL element 1 having the inverted structure shown in FIG.
[0316] To manufacture Figure 4 In the organic EL element 1 shown, the cathode 3 is first formed on the substrate 2 .
[0317] The cathode 3 can be formed by sputtering, vacuum deposition, sol-gel, spray pyrolysis (SPD), atomic layer deposition (ALD), vapor phase film formation, liquid phase film formation, etc. The cathode 3 can also be formed by bonding metal foils.
[0318] Next, an inorganic oxide layer 4 is formed on the cathode 3 .
[0319] The oxide layer 4 is formed by, for example, spray pyrolysis, sol-gel, sputtering, vacuum deposition, etc. The surface of the oxide layer 4 formed in this way may not be smooth but may have irregularities.
[0320] Next, the electron injection layer 5 is formed on the oxide layer 4 .
[0321] The electron injection layer 5 can be formed by the above-mentioned method for producing an organic thin film.
[0322] Next, the electron transport layer 10 , the light emitting layer 6 , and the hole transport layer 7 are sequentially formed on the electron injection layer 5 .
[0323] The method for forming the electron transport layer 10 , the light emitting layer 6 , and the hole transport layer 7 is not particularly limited, and various conventionally known formation methods can be appropriately used depending on the properties of the materials used for the electron transport layer 10 , the light emitting layer 6 , and the hole transport layer 7 .
[0324] Specifically, as methods for forming the electron transport layer 10, the light-emitting layer 6, and the hole transport layer 7, there can be cited: a coating method of applying an organic compound solution containing organic compounds constituting the electron transport layer 10, the light-emitting layer 6, and the hole transport layer 7, a vacuum evaporation method, an ESDUS (Evaporative Spray Deposition from Ultra-dilute Solution) method, and the like. Among these methods for forming the electron transport layer 10, the light-emitting layer 6, and the hole transport layer 7, the coating method is particularly preferably used. It should be noted that when the solvent solubility of the organic compounds constituting the electron transport layer 10, the light-emitting layer 6, and the hole transport layer 7 is low, it is preferred to use a vacuum evaporation method or an ESDUS method.
[0325] When the electron transport layer 10, the light-emitting layer 6, and the hole transport layer 7 are formed by a coating method, the organic compounds constituting the electron transport layer 10, the light-emitting layer 6, and the hole transport layer 7 are respectively dissolved in a solvent, thereby forming an organic compound solution containing the organic compounds constituting the electron transport layer 10, the light-emitting layer 6, and the hole transport layer 7, respectively.
[0326] As solvents for dissolving organic compounds constituting the electron transport layer 10, the light-emitting layer 6, and the hole transport layer 7, for example, preferred are aromatic hydrocarbon solvents such as xylene, toluene, cyclohexylbenzene, dihydrobenzofuran, trimethylbenzene, tetramethylbenzene, aromatic heterocyclic compound solvents such as pyridine, pyrazine, furan, pyrrole, thiophene, methylpyrrolidone, and aliphatic hydrocarbon solvents such as hexane, pentane, heptane, cyclohexane, and the like, and they can be used alone or in combination.
[0327] As a method for coating an organic compound solution containing an organic compound constituting the electron transport layer 10, the light emitting layer 6, and the hole transport layer 7, various coating methods such as spin coating, casting, micro gravure coating, gravure coating, rod coating, roller coating, wire bar coating, dip coating, spray coating, screen printing, flexographic printing, offset printing, and inkjet printing can be used. Among these coating methods, spin coating and slit coating are preferably used from the aspect of easier control of film thickness.
[0328] Next, the hole injection layer 8 and the anode 9 are formed in this order on the hole transport layer 7 .
[0329] When the hole injection layer 8 is composed of an inorganic material, the hole injection layer 8 can be formed in the same manner as the oxide layer 4 , for example.
[0330] When the hole transport layer 9 is composed of an organic material, the hole injection layer 8 can be formed, for example, in the same manner as the electron transport layer 10 , the light emitting layer 6 , and the hole transport layer 7 .
[0331] The anode 9 can be formed in the same manner as the cathode 3 , for example.
[0332] Through the above process, we can obtain Figure 4 The organic EL element 1 is shown.
[0333] Next, as an example of a method for producing an organic EL element of the present invention, Figure 5 A method for manufacturing the organic EL element 2 having the forward structure shown will be described.
[0334] To manufacture Figure 5 In the organic EL element 2 shown, first, the anode 9 is formed on the substrate 2 .
[0335] Anode 9 can be formed by sputtering, vacuum deposition, sol-gel, spray pyrolysis (SPD), atomic layer deposition (ALD), vapor phase film formation, liquid phase film formation, etc. Anode 9 can also be formed by bonding metal foils.
[0336] Next, the hole injection layer 8 is formed on the anode 9 .
[0337] The hole injection layer 8 can be formed by the above-mentioned method for producing an organic thin film.
[0338] Next, the hole transport layer 7 , the light emitting layer 6 , the electron transport layer 10 , and the electron injection layer 5 are sequentially formed on the hole injection layer 8 .
[0339] The formation methods of the hole transport layer 7, the light emitting layer 6, the electron transport layer 10, and the electron injection layer 5 are not particularly limited, and various conventionally known formation methods can be appropriately used according to the properties of the materials used in the hole transport layer 7, the light emitting layer 6, the electron transport layer 10, and the electron injection layer 5, respectively.
[0340] Specifically, as methods for forming the hole transport layer 7, the light-emitting layer 6, the electron transport layer 10, and the electron injection layer 5, there can be cited a coating method of an organic compound solution containing organic compounds constituting the hole transport layer 7, the light-emitting layer 6, the electron transport layer 10, and the electron injection layer 5, a vacuum evaporation method, ESDUS (ultra-dilute solution evaporation spray deposition method), and the like.
[0341] When a coating method is used to form the hole transport layer 7, the light-emitting layer 6, the electron transport layer 10, and the electron injection layer 5, the organic compounds constituting the hole transport layer 7, the light-emitting layer 6, the electron transport layer 10, and the electron injection layer 5 are respectively dissolved in a solvent to form an organic compound solution containing the organic compounds constituting the hole transport layer 7, the light-emitting layer 6, the electron transport layer 10, and the electron injection layer 5, respectively.
[0342] Examples of the solvent for dissolving the organic compounds constituting the hole transport layer 7, the light emitting layer 6, the electron transport layer 10, and the electron injection layer 5 include methyl ethyl ketone (MEK), acetone, diethyl ketone, methyl isobutyl ketone (MIBK), methyl isopropyl ketone (MIPK), diisobutyl ketone, 3,5,5-trimethylcyclohexanone, diacetone alcohol, cyclopentanone, ketone solvents such as cyclohexanone, methanol, ethanol, isopropanol, ethylene glycol, diethylene glycol (DEG), glycerol Alcohol solvents, diethyl ether, diisopropyl ether, 1,2-dimethoxyethane (DME), 1,4-dioxane, tetrahydrofuran (THF), tetrahydropyran (THP), anisole, diethylene glycol dimethyl ether (diglyme), diethylene glycol ethyl ether (carbitol) and other ether solvents, methyl cellosolve, ethyl cellosolve, phenyl cellosolve and other cellosolve solvents, hexane, pentane, heptane, cyclohexane and other aliphatic hydrocarbon solvents, toluene, xylene, benzene, cyclohexylbenzene, Aromatic hydrocarbon solvents such as dihydrobenzofuran, trimethylbenzene, tetramethylbenzene, etc., aromatic heterocyclic compound solvents such as pyridine, pyrazine, furan, pyrrole, thiophene, methylpyrrolidone, etc., amide solvents such as N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMA), halogenated solvents such as chlorobenzene, dichloromethane, chloroform, 1,2-dichloroethane, etc., ester solvents such as ethyl acetate, methyl acetate, ethyl formate, dimethyl sulfoxide (DMSO), cyclobutane Various organic solvents such as sulfur compound solvents such as sulfone, nitrile solvents such as acetonitrile, propionitrile, acrylonitrile, and organic acid solvents such as formic acid, acetic acid, trichloroacetic acid, and trifluoroacetic acid, etc., among which ketone solvents such as methyl ethyl ketone (MEK), acetone, diethyl ketone, methyl isobutyl ketone (MIBK), methyl isopropyl ketone (MIPK), diisobutyl ketone, 3,5,5-trimethylcyclohexanone, diacetone alcohol, and cyclopentanone are preferred, and they can be used alone or in combination.
[0343] As a method for coating an organic compound solution containing an organic compound constituting the hole transport layer 7, the light emitting layer 6, the electron transport layer 10, and the electron injection layer 5, various coating methods such as spin coating, casting, micro gravure coating, gravure coating, rod coating, roller coating, wire rod coating, dip coating, spray coating, screen printing, flexographic printing, offset printing, and inkjet printing can be used. Among these coating methods, spin coating and slit coating are preferably used from the aspect of easier control of film thickness.
[0344] Next, the cathode 3 is formed.
[0345] The cathode 3 can be formed in the same manner as the anode 9 , for example.
[0346] Through the above process, we can obtain Figure 5 The organic EL element 2 is shown.
[0347] "Sealing method"
[0348] In the right Figure 4 The organic EL element 1 shown, Figure 5 When the organic EL element 2 shown is sealed, the sealing can be performed by using a conventional method used for sealing an organic EL element.
[0349] Figure 4 The organic EL element 1 of the embodiment shown has an electron injection layer 5 composed of an organic thin film including the first material as the electron-donating organic material and the second material for transporting electrons, so that negative charges are generated by forming hydrogen bonds between the first material and the second material, thereby obtaining excellent electron injection properties. Therefore, the speed of electron injection / electron transport from the cathode 3 to the light-emitting layer 6 is fast and the driving voltage is low.
[0350] In addition, as described above, the organic thin film including the first material as an electron-donating organic material and the second material for transporting electrons is a laminated film, and the layer formed by the second material is a layer different from the electron injection layer formed by the first material, which is another embodiment of the organic EL element of the present invention. The organic EL element of such an embodiment also becomes an organic EL element 1 in which the speed of electron injection / electron transport from the cathode 3 to the light-emitting layer 6 is fast and the driving voltage is low.
[0351] in addition, Figure 5 In the organic EL element 2 of the embodiment shown, the first material as the electron-donating organic material forms a coordination bond with the adjacent cathode material, thereby generating negative charges and obtaining excellent electron injection properties. Therefore, the electron injection / electron transport speed from the cathode 3 to the light-emitting layer 6 is fast and the driving voltage is low.
[0352] In addition, as described above, an organic thin film including the first material as the electron-donating organic material and the second material as a compound that is difficult to inject electrons from the cathode even when an alkali metal is added is a laminated film, and the layer formed by the second material is a layer different from the electron injection layer formed by the first material, which is another embodiment of the organic EL element of the present invention. The organic EL element of such an embodiment also becomes an organic EL element 2 in which the speed of electron injection / electron transport from the cathode 3 to the light-emitting layer 6 is fast and the driving voltage is low.
[0353] "Other Examples"
[0354] The organic EL element of the present invention is not limited to the organic EL element described in the above embodiment.
[0355] Specifically, in the above-mentioned embodiment, the case where the organic thin film functions as the electron injection layer is cited as an example for explanation, but the organic EL element of the present invention only needs to have an organic thin film between the cathode and the light-emitting layer. Therefore, the organic thin film is not limited to the electron injection layer, and can also be set as a layer that serves as both the electron injection layer and the electron transport layer, and can also be set as the electron transport layer.
[0356] In addition, Figure 4 In the organic EL element 1 shown, the inorganic oxide layer 4 , the electron transport layer 10 , the hole transport layer 7 , and the hole injection layer 8 may be formed as necessary or may not be provided.
[0357] In addition, each of the cathode 3, oxide layer 4, electron injection layer 5, electron transport layer 10, light emitting layer 6, hole transport layer 7, hole injection layer 8 and anode 9 may be formed of one layer or two or more layers.
[0358] In addition, Figure 4 In the organic EL element 1 shown, it is possible to Figure 4 Other layers are provided between the layers shown. Specifically, an electron blocking layer or the like may be provided as necessary for the purpose of further improving the characteristics of the organic EL element.
[0359] In the above embodiment, an organic EL element of a reverse structure in which the cathode 3 is arranged between the substrate 2 and the light-emitting layer 6 is described as an example, but an element of a forward structure in which an anode is arranged between the substrate and the light-emitting layer may also be used.
[0360] Figure 5 In the organic EL element 2 of the forward structure shown, the electron transport layer 10 , the hole transport layer 7 , and the hole injection layer 8 may be formed as required or may not be provided.
[0361] Furthermore, each of the anode 9 , the hole injection layer 8 , the hole transport layer 7 , the light emitting layer 6 , the electron transport layer 10 , the electron injection layer 5 , and the cathode 3 may be formed of a single layer or may be composed of two or more layers.
[0362] in addition, Figure 5 In the organic EL element 2 shown in FIG. Figure 5 Other layers may be present between the layers shown. Specifically, a hole blocking layer or the like may be provided as necessary for the purpose of further improving the characteristics of the organic EL element.
[0363] The organic EL element of the present invention can change the emission color by appropriately selecting the material of the light-emitting layer, etc., and can also obtain a desired emission color by using a color filter, etc. Therefore, it can be suitably used as a light-emitting part of a display device or a lighting device.
[0364] The display device of the present invention includes the organic EL element of the present invention having an organic thin film between a cathode and a light-emitting layer, and has excellent productivity and low driving voltage. Therefore, it is suitable as a display device.
[0365] Furthermore, the lighting device of the present invention includes the organic EL element of the present invention which has excellent productivity and low driving voltage, and is therefore suitable as a lighting device.
[0366] The present invention is not limited to the above-mentioned embodiments, and the organic thin film of the present invention can be used in devices such as organic thin film solar cells, photoelectric conversion elements, and thin film transistors.
[0367] The organic thin film solar cell and photoelectric conversion element of the present invention include an organic thin film. For example, when the organic thin film is used for the electron injection layer of the organic thin film solar cell or photoelectric conversion element, a hydrogen bond is formed between the first material and the second material of the organic thin film, thereby generating negative charges, so that the speed of electron transmission is fast and high power generation efficiency can be obtained. Therefore, the organic thin film solar cell and photoelectric conversion element including the organic thin film of the present invention are preferred as organic thin film solar cells and photoelectric conversion elements.
[0368] In addition, the thin film transistor of the present invention includes an organic thin film. For example, when the channel layer of the thin film transistor is formed of an organic thin film, a channel layer with high electron mobility can be obtained.
[0369] Furthermore, when the organic thin film is formed on an electrode, it is expected that the contact resistance can be reduced.
[0370] Thus, the organic film of the present invention is suitable as a material for an organic thin film solar cell, a photoelectric conversion element, or a thin film transistor, and therefore, the compound having a structure represented by the above general formula (1) constituting the organic film is also suitable as a material for these. Such an organic thin film solar cell material, a photoelectric conversion element material, or a thin film transistor material containing a compound having a structure represented by the above general formula (1) is also one of the present invention.
[0371] Example
[0372] The present invention will be described in more detail below with reference to Examples, but the present invention is not limited to these Examples. It should be noted that, unless otherwise stated, "%" means "mol %".
[0373] Synthesis example 1
[0374] The boron-containing compound represented by the following formula (11) was synthesized by the method shown below.
[0375] [Chemistry 15]
[0376]
[0377] To a dichloromethane solution (0.3 ml) containing 5-bromo-2-(4-bromophenyl)pyridine (94 mg, 0.30 mmol) represented by formula (10) was added ethyl diisopropylamine (39 mg, 0.30 mmol) under an argon atmosphere. Boron tribromide (1.0 M dichloromethane solution, 0.9 ml, 0.9 mmol) was then added at 0°C, and the mixture was stirred at room temperature for 9 hours to react. The reaction solution was then cooled to 0°C, a saturated aqueous potassium carbonate solution was added, and the mixture was extracted with chloroform. The organic layer was then washed with saturated brine, dried over magnesium sulfate, and filtered. The filtrate was then concentrated using a rotary evaporator, the generated white solid was filtered out, and washed with hexane to obtain the boron-containing compound (40 mg, 0.082 mmol) represented by the above formula (11) at a yield of 28%.
[0378] Identification of the obtained boron-containing compounds using 1 H-NMR was used.
[0379] 1 H-NMR(CDCl3):7.57-7.59(m,2H),7.80(dd,J=8.4,0.6Hz,1H),7.99(s,1H),8.27(dd,J=8.4,2.1Hz,1H),9.01(d,J=1.5Hz,1H).
[0380] Synthesis example 2
[0381] Using the boron-containing compound represented by the above formula (11), a boron-containing compound represented by the following formula (12) was synthesized by the method shown below.
[0382] [Chemistry 16]
[0383]
[0384] Magnesium (561 mg, 23.1 mmol) was added to a 50 mL two-necked flask, and the reaction vessel was filled with nitrogen atmosphere. Cyclopentyl methyl ether (CPME) (10 mL) was then added, and a small amount of iodine was added, and the mixture was stirred until the color disappeared. A cyclopentyl methyl ether solution (9 mL) of 2,2'-dibromobiphenyl (3.0 g, 9.6 mmol) was then added dropwise to the reaction vessel, and the mixture was stirred at room temperature for 12 hours and at 50°C for 1 hour to prepare a Grignard reagent.
[0385] To another 200mL three-necked flask, add the boron-containing compound (3.71g, 7.7mmol) represented by the above formula (11), make the container into a nitrogen atmosphere, and add toluene (77mL). While stirring it at -78°C, add the above Grignard reagent at one time with a cannula. After stirring for 10 minutes, warm to room temperature and stir further for 12 hours. Add water to the reaction solution and extract with toluene. Wash the organic layer with saturated brine, dry with magnesium sulfate and filter. Thereafter, concentrate the filtrate and purify the residue by column chromatography to obtain 3.0g (yield 82%) of the boron-containing compound represented by the above formula (12).
[0386] Identification of the obtained boron-containing compounds using 1 H-NMR was used.
[0387] 1 H-NMR(CDCl3):6.85(d,J=7.04Hz,2H),7.05(t,J=7.19Hz,2H),7.32(t,J=7.48Hz,2H), 7.47(s,1H)7.49-7.57(m,1H),7.74-7.84(m,3H),7.90-8.00(m,2H),8.07-8.20(m,1H).
[0388] Synthesis example 3
[0389] Using the boron-containing compound represented by the above formula (12), a boron compound A represented by the following formula (14) was synthesized by the method shown below.
[0390] [Chemistry 17]
[0391]
[0392] A boron-containing compound represented by formula (12) (2.50 g, 5.26 mmol), 6-tri(n-butylstannyl)-2,2'-bipyridine (5.62 g, 12.6 mmol) represented by formula (13), Pd(PPh3)4 (610 mg, 0.53 mmol), and toluene (26 mL) were added to a 50 mL two-necked flask. A nitrogen atmosphere was then placed in the flask, and the mixture was stirred at 120°C for 24 hours to react. The reaction solution was then cooled to room temperature, concentrated, and the residue was purified by column chromatography to obtain 2.0 g (yield 60%) of a boron compound A represented by formula (14).
[0393] The obtained boron compound A was identified using 1 H-NMR was used.
[0394] 1H-NMR (CDCl3): 6.6.96 (d, J = 6.8 Hz, 2H), 7.04 (t, J = 7.2 Hz, 2H), 7.29-7.35 (m, 4H), 7.49 (d, J = 7.8 Hz, 1H), 7.73-7.85 (m, 7H), 8.01 (d, J = 0. 8Hz,1H),8.16(d,J=8.4Hz,1H),8.23(d,J=8.6Hz,1H),8.30-8.42(m,5H),8.60(d,J=8.0Hz,1H),8.66-8.67(m,2H),8.89(d,J=8.0Hz,1H).
[0395] Synthesis example 4
[0396] The compound represented by the following formula (15) was synthesized by the method shown below.
[0397] [Chemistry 18]
[0398]
[0399] In a 100 mL eggplant flask, a mixture of 4,7-dichloro-1,10-phenanthroline (3.00 g) and pyrrolidine (19.5 mL) was heated to reflux in a 100°C oil bath for 1 hour. The mixture returned to room temperature was concentrated under reduced pressure, and after adding water, ultrasonic treatment was performed, and the solid precipitated was filtered out. The obtained solid was dried under reduced pressure and dissolved in methanol (100 mL). Activated carbon was added to the mixture, and after stirring at room temperature for 1 hour, the insoluble matter was filtered out. The filtrate was concentrated under reduced pressure, and the obtained solid was recrystallized using methanol (9 mL). The obtained solid was washed with a small amount of methanol and dried under reduced pressure, thereby obtaining the compound represented by formula (15) (1.69 g, 44%) as a white solid.
[0400] Synthesis example 5
[0401] <Synthesis of Monomers for Boron-Containing Polymer Synthesis>
[0402] A compound represented by the following formula (16) (3.96 g), 4-pyridine boronic acid (1.03 g), Pd (PPh3) 4 (0.24 g), sodium carbonate (2.24 g), toluene (40 mL), distilled water (40 mL), and ethanol (20 mL) were added to a 300 mL reaction vessel. After stirring for 10 minutes while bubbling argon, the suspension was heated to 95 ° C in an oil bath and heated and stirred at this temperature for 18 hours. Water (100 mL) and toluene (100 mL) were added to the obtained yellow solution and divided into 2 layers. The organic layer was washed with water and saturated brine in sequence and then concentrated. The obtained residue was purified by column chromatography and preparative GPC to obtain a colorless solid. It was recrystallized from ethanol / hexane to obtain a compound represented by the following formula (17) (0.69 g).
[0403] [Chemistry 19]
[0404]
[0405] <Synthesis of Boron-Containing Polymer>
[0406] In an argon atmosphere, a compound represented by the above formula (17) (0.5 g), a compound represented by the following formula (18) (0.57 g), Pd(PPh3)4 (0.1 g), sodium carbonate (0.472 g), methyltrioctylammonium chloride (Aliquat336) (0.2 g), toluene (10 mL), and distilled water (10 mL) were added to a 50 mL pressure test tube. After bubbling argon for about 15 minutes, the suspension was heated at 100° C. in an oil bath and stirred for 24 hours. Iodobenzene (0.181 g) was added thereto, and after stirring at the same temperature for 18 hours, phenylboric acid (0.217 g) was added and stirred for 18 hours. The organic layer of the obtained dark brown suspension was filtered with diatomaceous earth, and the filtrate was concentrated. The obtained residue was column purified to obtain a light brown powder. Heptane and ethanol were added thereto, and the mixture was heated, dispersed and washed. After natural cooling, the solid was filtered out and washed with ethanol, thereby obtaining 0.61 g of a boron-containing polymer (9).
[0407] [Chemistry 20]
[0408]
[0409] Synthesis example 6
[0410] The compound represented by the following formula (19) was synthesized by the method shown below.
[0411] [Chemistry 21]
[0412]
[0413] In a 300 mL eggplant flask, a mixture of 4,7-dichloro-1,10-phenanthroline (3.00 g) and piperidine (47 mL) was heated and stirred in an oil bath at 120°C for 3 hours. Water (250 mL) was added to the mixture after returning to room temperature, and after stirring for 1 hour, the precipitate was filtered to obtain 4.47 g of the compound represented by formula (19) as a light brown solid.
[0414] Synthesis Example 7
[0415] The compound represented by the following formula (20) was synthesized by the method shown below.
[0416] [Chemistry 22]
[0417]
[0418] In a 200 mL eggplant flask, a mixture of 4,7-dichloro-1,10-phenanthroline (1.99 g) and morpholine (27.6 mL) was heated and stirred in an oil bath at 120°C for 3 hours. Water was added to the mixture returned to room temperature and extracted with chloroform. The separated organic layer was dried over anhydrous sodium sulfate and the unwanted substances were filtered out. The filtrate was concentrated under reduced pressure and the residue was washed with ethyl acetate to obtain the compound represented by formula (20) (2.03 g, 72%) as a light pink solid.
[0419] Embodiment 1, 2
[0420] Produced by the following method Figure 4 The organic EL element 1 shown was manufactured and evaluated.
[0421] [Process 1]
[0422] As the substrate 2, a commercially available transparent glass substrate having an average thickness of 0.7 mm and having an electrode (cathode 3) having a thickness of 150 nm and patterned to a width of 3 mm made of ITO was prepared.
[0423] Then, the substrate 2 with the cathode 3 was ultrasonically cleaned in acetone and isopropyl alcohol for 10 minutes each, and boiled in isopropyl alcohol for 5 minutes. Then, the substrate 2 with the cathode 3 was taken out from the isopropyl alcohol, dried by nitrogen blowing, and cleaned with UV ozone for 20 minutes.
[0424] [Process 2]
[0425] The substrate 2 on which the cathode 3 is formed after cleaning in [Step 1] is fixed on a substrate holder of a trocar sputtering device having a zinc metal target. The pressure in the chamber of the sputtering device is reduced to about 1×10 -4Pa, sputtering was performed under the condition of introducing argon gas and oxygen, and a zinc oxide layer (oxide layer 4) with a film thickness of about 7 nm was formed on the cathode 3 of the substrate 2. It should be noted that when the zinc oxide layer was formed, in order to remove the electrode, the zinc oxide film was not formed on a part of the ITO electrode (cathode 3). The substrate 2 with the oxide layer 4 formed was annealed at 400° C. for 1 hour in the atmosphere.
[0426] [Process 3]
[0427] Next, an organic thin film including a first material and a second material is formed as the electron injection layer 5 on the oxide layer 4 by the method described below.
[0428] First, the boron compound A and the phenanthroline derivative (weight ratio 1:0.05) synthesized in Synthesis Examples 1 to 3 are dissolved in cyclopentanone (concentration 1% by weight) to obtain a coating composition. Next, the substrate 2 formed with the cathode 3 and the oxide layer 4 prepared in [Step 2] is placed in a spin coater. Thereafter, while the coating composition is dripped onto the oxide layer 4, the substrate 2 is rotated at 3000 revolutions per minute for 30 seconds to form a coating film. Thereafter, an annealing treatment is performed at 120°C for 2 hours in a nitrogen atmosphere using a hot plate to form an electron injection layer 5. The average thickness of the obtained electron injection layer 5 is 20 nm.
[0429] Regarding the phenanthroline derivative as the first material, the following compound 1 was used in Example 1, and the following compound 2 was used in Example 2.
[0430] Compound 1 was synthesized with reference to known compounds described in European Journal of Organic Chemistry (2017), 2017, (14), 1902-1910. Compound 2 was a commercially available product.
[0431] [Chemistry 23]
[0432]
[0433] [Process 4]
[0434] Next, the substrate 2 on which each layer up to the electron injection layer 5 is formed is fixed on a substrate holder of a vacuum evaporation device. In addition, bis[2-(2-benzothiazolyl)phenol]zinc(II) (Zn(BTZ)2) represented by the following formula (24), tris[1-phenylisoquinoline]iridium(III) (Ir(piq)3) represented by the following formula (23), N,N'-di(1-naphthyl)-N,N'-diphenyl-1,1'-biphenyl-4,4'-diamine (α-NPD) represented by the following formula (22), N4,N4'-bis(dibenzo[b,d]thiophene-4-yl)-N4,N4'-diphenylbiphenyl-4,4'-diamine (DBTPB) represented by the following formula (21), 1,4,5,8,9,12-hexaazatriphenylene-2,3,6,7,10,11-hexacarbonitrile (HAT-CN) represented by the following formula (25), and Al were respectively loaded into an alumina crucible and set as a vapor deposition source.
[0435] [Chemistry 24]
[0436]
[0437] Then, the pressure in the chamber of the vacuum deposition device was reduced to 1×10 -5 The electron transport layer 10, the light emitting layer 6, the hole transport layer 7, the hole injection layer 8, and the anode 9 are continuously formed by a vacuum deposition method using resistance heating at a pressure of 1.25°C.
[0438] First, an electron transport layer 10 with a thickness of 10 nm composed of Zn(BTZ)2 is formed. Next, Zn(BTZ)2 is used as the main body and Ir(piq)3 is used as the dopant for 30 nm co-evaporation to form a light-emitting layer 6. At this time, the doping concentration of Ir(piq)3 is set to 6% by mass relative to the entire light-emitting layer 6. Next, 10 nm of DBTPB and 30 nm of α-NPD are formed on the substrate 2 on which the light-emitting layer 6 is formed to form a hole transport layer 7. A 10 nm HAT-CN is further formed to form a hole injection layer 8. Next, an anode 9 with a thickness of 100 nm composed of aluminum is formed on the substrate 2 on which the hole injection layer 8 is formed by vacuum evaporation.
[0439] It should be noted that the anode 9 was formed using a stainless steel vapor deposition mask in a strip-shaped manner with a vapor deposition surface of 3 mm in width, so that the light emitting area of the produced organic EL element was 9 mm. 2 .
[0440] [Process 5]
[0441] Next, the substrate 2 formed with each layer up to the anode 9 is placed in a glass cover (sealed container) having a concave space and sealed by filling a sealing material composed of an ultraviolet (UV) curing resin to obtain the organic EL elements of Examples 1 and 2.
[0442] Comparative Example 1
[0443] An organic EL device of Comparative Example 1 was prepared in the same manner as in Examples 1 and 2 except that the phenanthroline derivative was not used.
[0444] For the components of Examples 1, 2 and Comparative Example 1 thus obtained, voltage was applied using a "2400 SourceMeter" manufactured by Keithley, Inc., and brightness was measured using an "LS-100" manufactured by Konica Minolta, Inc., to investigate the relationship between applied voltage and brightness. In addition, the relationship between applied voltage and current density was investigated. Further, the relationship between current density and external quantum efficiency was calculated based on the obtained brightness-voltage-current value correlation. These results are shown in Figures 15 to 17 .
[0445] Depend on Figures 15 to 17 It can be seen that, compared with the element of Comparative Example 1, in the elements of Examples 1 and 2 in which the phenanthroline derivative is doped in the electron injection layer, high brightness is obtained at a low applied voltage, and the external quantum efficiency is also high. In addition, when Example 1 is compared with Example 2, Example 1 using a phenanthroline derivative with a large electrostatic potential obtains better characteristics than Example 2. It is believed that this is because the phenanthroline derivative acts as an n-type dopant that causes the boron compound to generate negative charges, thereby improving the electron injection and transport properties.
[0446] Embodiments 3 to 5
[0447] An organic thin film containing the first material and the second material is formed as an electron injection layer 5 on the oxide layer 4 by the method shown below. The substrate 2 formed to the oxide 4 is fixed on the substrate holder of the vacuum evaporation device. Then, an organic thin film with a film thickness of 10 nm containing the boron compound A and the phenanthroline derivative (weight ratio 1:0.05) is formed by co-evaporation. Except for this, the organic EL elements of Examples 3 to 5 are prepared by the same method as Example 1.
[0448] As for the phenanthroline derivative as the first material, the following compound 3 was used in Example 3, the following compound 4 was used in Example 4, and the above-mentioned compound 2 was used in Example 5. Both compounds 3 and 4 were commercially available products.
[0449] [Chemistry 25]
[0450]
[0451] Comparative Example 2
[0452] An organic EL device of Comparative Example 2 was produced in the same manner as in Examples 3 to 5 except that the phenanthroline derivative was not used.
[0453] For the components of Examples 3 to 5 and Comparative Example 2 thus obtained, voltage was applied using a "2400 SourceMeter" manufactured by Keithley, Inc., and brightness was measured using an "LS-100" manufactured by Konica Minolta, Inc., to investigate the relationship between applied voltage and brightness. In addition, the relationship between applied voltage and current density was investigated. Further, the relationship between current density and external quantum efficiency was calculated based on the obtained brightness-voltage-current value correlation. These results are shown in Figures 18 to 20 .
[0454] Depend on Figures 18 to 20 It can be seen that, compared with the element of Comparative Example 2, in the elements of Examples 3 to 5 in which the phenanthroline derivative is doped in the electron injection layer, high brightness is obtained at a low applied voltage, and the external quantum efficiency is also high. In addition, when comparing Examples 3 to 5, the examples using the phenanthroline derivative with a large electrostatic potential obtain good characteristics. It is believed that this is because the phenanthroline derivative acts as an n-type dopant that causes the boron compound to generate negative charges, thereby improving the electron injection and transport properties.
[0455] Example 6
[0456] An organic thin film comprising the first material and the second material is formed on the oxide layer 4 as an electron injection layer 5 by the method shown below. The substrate 2 formed to the oxide 4 is fixed on the substrate frame of the vacuum evaporation device. Thereafter, an organic thin film having a film thickness of 5 nm is formed by co-evaporation comprising the boron compound A and the above-mentioned compound 2 (weight ratio 1:0.05). An organic thin film having a film thickness of 5 nm consisting only of the boron compound is further formed to form an electron injection layer 5 having a total thickness of 10 nm. In addition, the organic EL element of Example 6 is prepared by the same method as in Example 1.
[0457] Example 7
[0458] An organic thin film containing the first material and the second material is formed on the oxide layer 4 as an electron injection layer 5 by the method shown below. The substrate 2 formed to the oxide 4 is fixed on the substrate holder of the vacuum evaporation device. An organic thin film with a film thickness of 5 nm consisting only of the boron compound A is formed, and then an organic thin film with a film thickness of 5 nm containing the boron compound and the above-mentioned compound 2 (weight ratio 1:0.05) is formed by co-evaporation to form a total of 10 nm of the electron injection layer 5. Except for this, the organic EL element of Example 7 is prepared by the same method as Example 1.
[0459] For the components of Examples 6 and 7 thus obtained, voltage was applied using a "2400 SourceMeter" manufactured by Keithley, Inc., and brightness was measured using an "LS-100" manufactured by Konica Minolta, Inc., to investigate the relationship between applied voltage and brightness. In addition, the relationship between applied voltage and current density was investigated. Further, the relationship between current density and external quantum efficiency was calculated based on the obtained brightness-voltage-current value correlation. These results were compared with Comparative Example 2. The results are shown in Figures 21 to 23 In addition, the brightness was measured while the components of Examples 6 and 7 were continuously driven. The results are shown in Fig.24 .
[0460] Depend on Figures 21 to 23 It can be seen that when comparing Examples 6 and 7, Example 6 in which Compound 2 is doped on the layer side close to the oxide layer 4 in the electron injection layer obtains slightly better characteristics. It is believed that the reason lies in the interaction between phenanthroline and the oxide layer as reported in non-patent literatures 10 and 11. On the other hand, in Example 7, which does not contain Compound 2 near the oxide layer 4, a significant voltage reduction is also observed compared with Comparative Example 2. It is believed that this is due to the fact that the phenanthroline derivative acts as an n-type dopant that causes the boron compound to generate negative charges, thereby improving the electron injection and transport properties. In Examples 1 to 6, the effect of the interaction between phenanthroline and the oxide layer 4 is also believed to contribute to the low voltage, but as shown in Example 7, a significant voltage reduction brought about by the phenanthroline derivative is also observed in a system that does not interact with the substrate. This result shows the rationality of promoting electron injection by forming hydrogen bonds proposed in the present invention.
[0461] in addition, Fig.24 The luminance decay when the elements of Examples 6 and 7 are driven continuously is shown. Fig.24 It can be confirmed that Example 7, in which the substrate and the phenanthroline derivative did not interact, had a longer life than Example 6, in which the substrate and the phenanthroline derivative interacted. Based on this result, it can be said that when the substrate and the phenanthroline derivative interact, the stability of the material is impaired; on the other hand, Example 6, which utilizes hydrogen bonding, is suitable for further extending the life.
[0462] Example 8
[0463] An organic thin film containing the first material and the second material is formed on the oxide layer 4 together with other materials as an electron injection layer 5 by the method shown below. First, the boron-containing polymer (9) synthesized in the above-mentioned synthesis example 5 is dissolved in DMF (concentration of 0.1 weight%) to obtain a coating composition. Next, the substrate 2 formed to the oxide 4 is set in a spin coater. Thereafter, while the coating composition is dripped onto the oxide layer 4, the substrate 2 is rotated at 3000 revolutions per minute for 30 seconds to form a 5nm coating film. Thereafter, an annealing treatment is performed at 120°C for 2 hours under a nitrogen atmosphere using a hot plate, and the obtained substrate 2 is fixed to the substrate frame of a vacuum evaporation device. Thereafter, an organic thin film with a film thickness of 5nm containing the boron compound A and the above-mentioned compound 1 (weight ratio 1:0.05) is formed by co-evaporation to form an electron injection layer 5 with a total of 10nm. In addition, the organic EL element of Example 8 is prepared by the same method as Example 1.
[0464] For the element of Example 8 thus obtained, voltage was applied using the "2400 SourceMeter" manufactured by Keithley, and brightness was measured using the "LS-100" manufactured by Konica Minolta, to investigate the relationship between applied voltage and brightness. In addition, the relationship between applied voltage and current density was investigated. Further, the relationship between current density and external quantum efficiency was calculated based on the obtained brightness-voltage-current value correlation. These results were compared with those of Example 1. The results are shown in Figures 25-27 Furthermore, the brightness of the device of Example 8 was measured while continuously driving, and compared with the device of Example 1. The results are shown in Fig.28 .
[0465] Depend on Figures 25-27 It is known that when comparing Example 1 with Example 8, Example 1 in which Compound 1 is doped on the layer side near the oxide layer 4 in the electron injection layer obtains better characteristics. It is believed that the reason is the interaction between phenanthroline and the oxide layer as reported in non-patent literatures 10 and 11. On the other hand, in Example 8, which does not contain Compound 1 near the oxide layer 4, a significant voltage reduction is also observed compared with Comparative Example 2. It is believed that this is due to the fact that the phenanthroline derivative acts as an n-type dopant that causes the boron compound to generate a negative charge, thereby improving the electron injection and transport properties. Similarly to Example 7, a significant voltage reduction brought about by the phenanthroline derivative is also observed in a system that does not interact with the substrate. This result shows the rationality of promoting electron injection by forming hydrogen bonds proposed in the present invention.
[0466] in addition, Fig.28 The luminance decay when the elements of Examples 1 and 8 are driven continuously is shown. Fig.28It can be confirmed that the life of Example 8, in which the substrate and the phenanthroline derivative do not interact due to the presence of the polymer, is longer than that of Example 1, in which the substrate and the phenanthroline derivative interact. Based on this result, it can be said that when the substrate and the phenanthroline derivative interact, the stability of the material is impaired; in contrast, Example 8, which utilizes hydrogen bonding, is suitable for further extending the life. In this way, even if a material other than the main material of the doping layer is used between the electrode (oxide) and the doping layer, the life of the element can be extended.
[0467] Examples 9 to 13, Comparative Example 3
[0468] Next, in order to verify that electron injection can be performed only by the phenanthroline derivative, an organic thin film composed only of the first material is formed on the oxide layer 4 as the electron injection layer 5 by the method shown below. In Examples 9 to 13 and Comparative Example 3, the steps [Step 1] and [Step 2] of forming the oxide layer 4 and the steps [Step 4] and [Step 5] after forming the electron injection layer 5 are performed in the same manner as in Example 1, and an organic EL element is produced.
[0469] Example 9: Compound 3 with a thickness of 10 nm was deposited by vacuum evaporation.
[0470] Example 10: Compound 2 with a thickness of 10 nm was deposited by vacuum evaporation.
[0471] Example 11: Compound 1 with a thickness of 10 nm was deposited by vacuum evaporation.
[0472] Example 12: The compound represented by formula (15) was deposited in a thickness of 10 nm by vacuum deposition.
[0473] Example 13: The compound represented by formula (15) is dissolved in cyclopentanone (concentration of 0.5 wt%) to obtain a coating composition. Next, the substrate 2 formed with the cathode 3 and the oxide layer 4 prepared in [Step 2] is placed in a spin coater. Thereafter, the coating composition is dripped onto the oxide layer 4 while the substrate 2 is rotated at 3000 revolutions per minute for 30 seconds to form a coating film. Thereafter, an annealing treatment is performed at 120° C. for 2 hours in a nitrogen atmosphere using a hot plate to form an electron injection layer 5. The average thickness of the obtained electron injection layer 5 is 10 nm.
[0474] Comparative Example 3: Lithium fluoride of 1 nm and the compound represented by the formula (14) of 10 nm were deposited by vacuum deposition.
[0475] For the elements of Examples 9 to 13 and Comparative Example 3 thus obtained, voltage was applied using a "2400 SourceMeter" manufactured by Keithley, Inc., and brightness was measured using an "LS-100" manufactured by Konica Minolta, Inc., to investigate the relationship between applied voltage and brightness. The results are shown in Fig.29 In addition, microscopic images of the light-emitting surfaces of the components of Examples 12, 13 and Comparative Example 3 when stored in the atmosphere without sealing are shown in FIG. Fig.30 .
[0476] according to Fig.29 The results shown show that, compared with Comparative Example 3 in which lithium fluoride and an electron transport material are used for the electron injection layer 5, in Examples 9 to 13 in which a phenanthroline derivative is used for the electron injection layer 5, high brightness is obtained at a low driving voltage. Therefore, it can be seen that even when a phenanthroline derivative is used alone in the electron injection layer, high electron injectability can be obtained. In addition, according to the comparison of the characteristics of Example 12 and Example 13, when the electron injection layer is formed by coating, good electron injectability is obtained. It is believed that this is because, as described in Non-Patent Literature 12, the oxide located below the electron injection layer 5 is dissolved due to the coating of the electron injection layer 5, increasing the coordination number with phenanthroline.
[0477] In addition, by Fig.30 The results shown show that, compared with the element of Comparative Example 3 using lithium fluoride, the elements of Examples 12 and 13 have a slow degradation rate of the light-emitting surface in the presence of oxygen and moisture, and have high resistance to oxygen and moisture. This is considered to show the superiority of the electron injection layer using a phenanthroline derivative that can inject electrons without using an unstable alkali metal.
[0478] Examples 14 to 16, Comparative Examples 4 to 6
[0479] The phenanthroline derivative as the first material was prepared by the following method using the compound represented by formula (15) and the commercially available compound 2. Figure 5 The organic EL device 2 with the forward structure shown was evaluated.
[0480] [Process 1]
[0481] As the substrate 2 , a commercially available transparent glass substrate having an average thickness of 0.7 mm and having an electrode (anode 9 ) formed of ITO having a thickness of 100 nm and patterned to a width of 3 mm was prepared.
[0482] Then, the substrate 2 with the anode 9 was ultrasonically cleaned in acetone and isopropyl alcohol for 10 minutes each, and boiled in isopropyl alcohol for 5 minutes. Then, the substrate 2 with the anode 9 was taken out from the isopropyl alcohol, dried by nitrogen blowing, and cleaned with UV ozone for 20 minutes.
[0483] [Process 2]
[0484] The substrate 2 with the anode 9 formed thereon after cleaning in [Step 1] was placed in a spin coater, and a hole injection material "Clevios HIL1.3N" manufactured by Heraeus was formed into a film with a thickness of 10 nm as the hole injection layer 8. The film was then heated on a hot plate heated to 180°C for 1 hour.
[0485] [Process 3]
[0486] Next, the substrate 2 on which the hole injection layer 8 has been formed is fixed to a substrate holder of a vacuum deposition apparatus.
[0487] In addition, 2,4-diphenyl-6-bis((12-phenylindole)[2,3-a]carbazole-11-yl)-1,3,5-triazine (DIC-TRZ) represented by the following formula (26), fac-tris(3-methyl-2-phenylpyridine-N,C2'-)iridium(III) (Ir(mppy)3) represented by the following formula (27), N,N'-di(1-naphthyl)-N,N'-diphenyl-1,1'-biphenyl-4,4-diol represented by the above formula (22) were used. '-diamine (α-NPD), N3,N3"'-bis(dibenzo[b,d]thiophene-4-yl)-N3,N3"'-diphenyl-[1,1':2',1":2",1"'-quaterphenyl]-3,3"'-diamine (4DBTP3Q) represented by the following formula (28), the compound represented by formula (15) as the first material and the commercially available compound 2, various materials as the second material shown below and Al are placed in an alumina crucible and set as a vapor deposition source.
[0488] [Chemistry 26]
[0489]
[0490] Regarding the second material, the compound represented by the above formula (14) is used as an example of a boron-containing compound, the compound represented by the following formula (29) is used as an example of a compound containing pyridine, and the compound represented by the following formula (30) (commercially available) is used as a compound having a heterocyclic ring containing a carbonyl group.
[0491] [Chemistry 27]
[0492]
[0493] Then, the pressure in the chamber of the vacuum deposition device was reduced to 1×10 -5 Pa, the hole transport layer 7, the light emitting layer 6, the electron transport layer 10, the electron injection layer 5, and the cathode 3 are continuously formed by a vacuum deposition method using resistance heating.
[0494] Specifically, first, a hole transport layer 7 having a thickness of 30 nm and composed of 20 nm of α-NPD and 10 nm of 4DBTP3Q was formed.
[0495] Next, DIC-TRZ was used as a host and Ir(mppy)3 was used as a dopant by co-evaporation at 25 nm to form a light-emitting layer 6. At this time, the doping concentration of Ir(mppy)3 was set to 3 mass % relative to the entire light-emitting layer 6.
[0496] Next, the electron transport layer 10 with a thickness of 40 nm and the electron injection layer 5 with a thickness of 1 nm were formed on the substrate 2 on which the light emitting layer 6 was formed.
[0497] Then, a cathode 3 with a film thickness of 100 nm made of aluminum is formed by vacuum evaporation on the substrate 2 formed with the electron injection layer 5. It should be noted that the cathode 3 is formed in a strip shape with a width of 3 mm using a stainless steel evaporation mask, so that the light emitting area of the produced organic EL element is 9 mm. 2 .
[0498] In each example, the compounds used as the second material (electron transport layer) and the first material (electron injection layer) are as follows.
[0499] Example 14: The compound of formula (14) is used as the second material, and the compound of formula (15) is used as the first material.
[0500] Example 15: The compound of formula (29) is used as the second material, and the compound of formula (15) is used as the first material.
[0501] Example 16: The compound of formula (30) is used as the second material, and the compound of formula (15) is used as the first material.
[0502] In addition, in each comparative example, the compounds used as the second material (electron transport layer) and the first material (electron injection layer) are as follows.
[0503] Comparative Example 4: The compound of formula (14) was used as the second material, and lithium fluoride was used as the first material.
[0504] Comparative Example 5: The compound of formula (29) was used as the second material, and lithium fluoride was used as the first material.
[0505] Comparative Example 6: The compound of formula (30) was used as the second material, and lithium fluoride was used as the first material.
[0506] [Process 4]
[0507] Next, the substrate 2 formed with the layers up to the cathode 3 is placed in a glass cover (sealed container) having a concave space and sealed by filling a sealing material composed of an ultraviolet (UV) curable resin to obtain each organic EL element.
[0508] The brightness-voltage characteristics of the elements of Examples 14 to 16 and Comparative Examples 4 to 6 were measured by the same method as in the other Examples and Comparative Examples, and the results are shown in FIG. Fig.31 , 33 , 34, while continuously driving the elements of Example 14 and Comparative Example 4, the brightness was measured and the results are shown in Fig.32 .
[0509] In the example of using a boron-containing compound as the second material, in Example 14, which is the result of using the compound of formula (14), attention is paid to Fig.31 From the above, Example 14 in which the phenanthroline derivative represented by formula (15) is used for the electron injection layer 8 and Comparative Example 4 in which lithium fluoride is used for the electron injection layer 8 obtain the same brightness-voltage characteristics. It can be said that when the phenanthroline derivative represented by formula (15) is used for the organic EL element of the forward structure, the electron injection property equivalent to that of lithium fluoride can be obtained. In addition, attention should be paid to Fig.32 The driving stability shown in FIG. 1 is similar to that of lithium fluoride. Therefore, by using a phenanthroline derivative, an organic EL element that can operate at a low driving speed without using an alkali metal and has excellent driving stability can be realized.
[0510] In an example of using a compound containing pyridine as the second material, in Example 15, which is a result of using a compound of formula (29), attention is paid to Fig.33 From this, it can be seen that Example 15 in which the phenanthroline derivative represented by structural formula (15) is used for the electron injection layer 8 and Comparative Example 5 in which lithium fluoride is used for the electron injection layer 8 also obtain equivalent brightness-voltage characteristics.
[0511] Next, as an example of a compound having a heterocyclic ring containing a carbonyl group, attention is paid to Example 16 using a compound of formula (30). Fig.34 In, with Fig.31 , 33 In contrast, Example 16 obtained high luminance at a low applied voltage compared to Comparative Example 6 using LiF. This result can be considered to reflect the excellent electron injection property of the phenanthroline derivative.
[0512] Examples 17 to 20, Comparative Example 7
[0513] The organic EL devices with a forward structure were prepared and evaluated by the following method. Figure 6The organic EL element of the laminated structure shown in the example 18 is Figure 7 An organic EL element with a layered structure as shown.
[0514] [Process 1]
[0515] As the substrate 2 , a commercially available transparent glass substrate having an average thickness of 0.7 mm and having an electrode (anode 9 ) formed of ITO having a thickness of 100 nm and patterned to a width of 3 mm was prepared.
[0516] Then, the substrate 2 with the anode 9 was ultrasonically cleaned in acetone and isopropyl alcohol for 10 minutes each, and boiled in isopropyl alcohol for 5 minutes. Then, the substrate 2 with the anode 9 was taken out from the isopropyl alcohol, dried by nitrogen blowing, and cleaned with UV ozone for 20 minutes.
[0517] [Process 2]
[0518] The substrate 2 with the anode 9 formed thereon after cleaning in [Step 1] was placed in a spin coater, and a hole injection material "Clevios HIL1.3N" manufactured by Heraeus was formed into a film with a thickness of 10 nm as the hole injection layer 8. The film was then heated on a hot plate heated to 180°C for 1 hour.
[0519] [Process 3]
[0520] Next, the substrate 2 on which the hole injection layer 8 has been formed is fixed to a substrate holder of a vacuum deposition apparatus.
[0521] In addition, DIC-TRZ, Ir(mppy)3, α-NPD, 4DBTP3Q, the compound represented by formula (15) as the first material, lithium fluoride (LiF), and Al were placed in alumina crucibles and set as evaporation sources.
[0522] Then, the pressure in the chamber of the vacuum deposition device was reduced to 1×10 -5 Pa, the hole transport layer 7, the light emitting layer 6, the electron transport layer 10, the electron injection layer 5, and the cathode 3 are continuously formed by a vacuum deposition method using resistance heating.
[0523] Specifically, first, a hole transport layer 7 having a thickness of 30 nm and composed of 20 nm of α-NPD and 10 nm of 4DBTP3Q was formed.
[0524] Next, DIC-TRZ was used as a host and Ir(mppy)3 was used as a dopant by co-evaporation at 25 nm to form a light-emitting layer 6. At this time, the doping concentration of Ir(mppy)3 was set to 3 mass % relative to the entire light-emitting layer 6.
[0525] Next, an electron transport layer 10 composed of DIC-TRZ with a thickness of 40 nm and an electron injection layer 5 with a thickness of 1 nm were formed on the substrate 2 on which the light emitting layer 6 was formed.
[0526] In Example 17, the compound represented by the formula (15) was used in the electron injection layer 5 , and in Comparative Example 7, LiF, which is a common electron injection material, was used in the electron injection layer 5 .
[0527] In Example 18, DIC-TRZ was used in the hole transport layer 7 having a thickness of 30 nm, and the other layers were the same as those in Example 17.
[0528] In Example 19, the compound represented by the formula (19) was used in the electron injection layer. In Example 20, the compound represented by the formula (20) was used in the electron injection layer. The other aspects were the same as in Example 17.
[0529] The brightness-voltage characteristics of the elements of Examples 17 to 20 and Comparative Example 7 were measured by the same method as the other Examples and Comparative Examples, and the results are shown in FIG. Fig.35 .
[0530] Examples 17, 19, and 20 using the compound represented by the general formula (1) of the present invention as the electron injection layer operate at a driving voltage equal to or higher than that of LiF used in Comparative Example 7, which indicates that the compound represented by the general formula (1) of the present invention can be effectively used as an electron injection layer. In Examples 17 and 19, electrons can be injected particularly effectively, and it can be seen that they can operate at a lower driving voltage than the electron injection layer using LiF. In addition, it can be seen that Example 18, in which the hole transport layer is DIC-TRZ as the main body of the light-emitting layer, also operates at a driving voltage equal to that of Example 17. In this way, by using a material with excellent electron injection properties, the structure of the organic EL element can be simplified and the number of materials required can be reduced.
[0531] Example 21, Comparative Example 8
[0532] Example 18 has a structure in which the light-emitting layer is formed of two materials, the host and the dopant, in order to verify that an organic EL element having a light-emitting layer composed of one material can also be realized. Figure 7 Using the simple structure shown, elements of Example 21 and Comparative Example 8 were produced.
[0533] [Process 1]
[0534] As the substrate 2 , a commercially available transparent glass substrate having an average thickness of 0.7 mm and having an electrode (anode 9 ) formed of ITO having a thickness of 100 nm and patterned to a width of 3 mm was prepared.
[0535] Then, the substrate 2 with the anode 9 was ultrasonically cleaned in acetone and isopropyl alcohol for 10 minutes each, and boiled in isopropyl alcohol for 5 minutes. Then, the substrate 2 with the anode 9 was taken out from the isopropyl alcohol, dried by nitrogen blowing, and cleaned with UV ozone for 20 minutes.
[0536] [Process 2]
[0537] Next, the substrate 2 is fixed on a substrate frame of a vacuum evaporation device.
[0538] In addition, fullerene used as the hole injection layer 8, (9,10-bis(4-(9H carbazole-9-yl)-2,6-dimethylphenyl))-9,10-diboranthracene (CzDBA) represented by the following formula (31), a compound represented by formula (15) as the first material, lithium quinoline, and Al were respectively loaded into an alumina crucible and set as a vapor deposition source. In addition, molybdenum trioxide used in the hole injection layer 8 was placed in a tungsten plate and set.
[0539] [Chemistry 28]
[0540]
[0541] Then, the pressure in the chamber of the vacuum deposition device was reduced to 1×10 -5 Pa pressure, and each layer was continuously evaporated by a vacuum evaporation method based on resistance heating. As the hole injection layer 8, molybdenum trioxide and fullerene were evaporated with a thickness of 5nm, respectively, and as the combined layer of the hole transport layer 7, the light-emitting layer 6 and the electron transport layer 10, only CzDBA was evaporated with a thickness of 75nm, and then the electron injection layer 5 and the cathode 3 with a film thickness of 1nm were continuously formed. In Example 21, the compound represented by formula (15) was used in the electron injection layer 5, and in Comparative Example 8, lithium quinoline, which is a common electron injection material, was used in the electron injection layer 5.
[0542] The brightness-voltage characteristics of the elements of Example 21 and Comparative Example 8 were measured by the same method as the other examples and comparative examples. The results are shown in FIG. Fig.36 .
[0543] It can be seen that in Comparative Example 8, it is difficult to inject electrons from lithium quinoline to CzDBA, so the driving voltage is high; on the contrary, in Example 21, electrons can be effectively injected and the device can operate at a low driving voltage. In this way, by using a material with excellent electron injection properties, the structure of the organic EL element can be simplified and the number of required materials can be reduced.
[0544] Explanation of symbols
[0545] 1: organic EL element, 2: substrate, 3: cathode, 4: oxide layer, 5: electron injection layer, 6: light emitting layer, 7: hole transport layer, 8: hole injection layer, 9: anode, 10: electron transport layer.
Claims
1. An organic thin film, characterized in that: It is a single-layer film comprising a first material and a second material for transporting electrons, or a laminated film comprising a film comprising the first material and a film comprising the second material, wherein the first material is a phenanthroline compound having a structure represented by the following general formula (2): In the general formula (2), R 4 , R 5 are the same or different, and represent a dialkylamino group or an alkoxy group located at the 4th and 7th positions of the phenanthroline ring, wherein the dialkylamino group is a dialkylamino group having an alkyl group having 1 to 10 carbon atoms, and the alkoxy group is a methoxy group or an ethoxy group; m 4 、m 5 All represent 1, The second material is an organic material.
2. The organic thin film according to claim 1, characterized in that The ratio of the first material to the second material is 0.1:99.9 to 20:1 in terms of the mass ratio of the first material to the second material.
3. The organic thin film according to claim 1, characterized in that The ratio of the first material to the second material is 0.5:99 to 10:1 in terms of the mass ratio of the first material to the second material. 4 . A laminated film comprising an oxide layer and the organic thin film layer according to claim 1 formed on the oxide layer.
5. An organic electroluminescent element having a light-emitting layer between a cathode and an anode, characterized in that: The organic thin film according to claim 1 or the laminated film according to claim 4 is provided between the cathode and the light-emitting layer.
6. The organic electroluminescent element according to claim 5, wherein: An inorganic oxide layer is provided between the cathode and the organic film.
7. The organic electroluminescent element according to claim 5, characterized in that: A laminated film of a film including the first material and the second material and a film including the second material is provided between the cathode and the light-emitting layer.
8. The organic electroluminescent element according to claim 7, wherein: A layer including the second material is provided between the light-emitting layer and the film including the first material and the second material.
9. The organic electroluminescent element according to claim 7, wherein: A layer including the second material is provided between the cathode and the film including the first material and the second material.
10. The organic electroluminescent element according to claim 5, wherein: A layer containing the second material is provided between the anode and the light-emitting layer.
11. The organic electroluminescent element according to claim 5, wherein: The light-emitting layer includes the second material.
12. Use of a phenanthroline compound having a structure represented by the following general formula (2) as an electron injecting material for an organic electroluminescent device, In the general formula (2), R 4 , R 5 are the same or different, and represent a dialkylamino group or an alkoxy group located at the 4th and 7th positions of the phenanthroline ring, wherein the dialkylamino group is a dialkylamino group having an alkyl group having 1 to 10 carbon atoms, and the alkoxy group is a methoxy group or an ethoxy group; m 4 、m 5 All represent 1.
13. An organic electroluminescent element having a light-emitting layer between a cathode and an anode, characterized in that: A layer containing an electron-injecting material for an organic electroluminescent device using the phenanthroline compound according to claim 12 is provided as an electron-injecting layer between the cathode and the anode and between the cathode and the light-emitting layer.
14. The organic electroluminescent element according to claim 13, wherein: An inorganic oxide layer is provided between the cathode and the layer containing the electron injecting material for an organic electroluminescent device using the phenanthroline compound according to claim 12 .
15. A display device, characterized in that: The device comprises the organic electroluminescent element according to any one of claims 5 to 11, 13, and 14.
16. A lighting device, characterized in that: The device comprises the organic electroluminescent element according to any one of claims 5 to 11, 13, and 14.
17. Use of a phenanthroline compound having a structure represented by the following general formula (2) as an electron injecting material for an organic thin film solar cell, In the general formula (2), R 4 , R 5 are the same or different, and represent a dialkylamino group or an alkoxy group located at the 4th and 7th positions of the phenanthroline ring, wherein the dialkylamino group is a dialkylamino group having an alkyl group having 1 to 10 carbon atoms, and the alkoxy group is a methoxy group or an ethoxy group; m 4 、m 5 All represent 1.
18. An organic thin film solar cell, characterized in that: The electron injection layer comprises any one of the organic thin film according to claim 1, the laminated film according to claim 4, or a layer comprising an electron injection material for an organic thin film solar cell using a phenanthroline compound according to claim 17.
19. Use of a phenanthroline compound having a structure represented by the following general formula (2) as an electron injecting material for a photoelectric conversion element, In the general formula (2), R 4 , R 5 are the same or different, and represent a dialkylamino group or an alkoxy group located at the 4th and 7th positions of the phenanthroline ring, wherein the dialkylamino group is a dialkylamino group having an alkyl group having 1 to 10 carbon atoms, and the alkoxy group is a methoxy group or an ethoxy group; m 4 、m 5 All represent 1.
20. A photoelectric conversion element, characterized in that: The electron injection layer comprises any one of the organic thin film according to claim 1, the laminated film according to claim 4, or a layer comprising an electron injection material for a photoelectric conversion element using the phenanthroline compound according to claim 19.
21. Use of a phenanthroline compound having a structure represented by the following general formula (2) as an electron injecting material for a thin film transistor, In the general formula (2), R 4 , R 5 are the same or different, and represent a dialkylamino group or an alkoxy group located at the 4th and 7th positions of the phenanthroline ring, wherein the dialkylamino group is a dialkylamino group having an alkyl group having 1 to 10 carbon atoms, and the alkoxy group is a methoxy group or an ethoxy group; m 4 、m 5 All represent 1.
22. A thin film transistor, characterized in that: The electron injection layer comprises any one of the organic thin film according to claim 1, the laminated film according to claim 4, or a layer comprising an electron injection material for a thin film transistor using the phenanthroline compound according to claim 21.
23. A coating composition, characterized in that It comprises a first material and a second material for transporting electrons, wherein the first material is a phenanthroline compound having a structure represented by the following general formula (2): In the general formula (2), R 4 , R 5 are the same or different, and represent a dialkylamino group or an alkoxy group located at the 4th and 7th positions of the phenanthroline ring, wherein the dialkylamino group is a dialkylamino group having an alkyl group having 1 to 10 carbon atoms, and the alkoxy group is a methoxy group or an ethoxy group; m 4 、m 5 All represent 1, The second material is an organic material.
24. Use of a phenanthroline compound having a structure represented by the following general formula (2) in an electron injecting coating composition, In the general formula (2), R 4 , R 5 are the same or different, and represent a dialkylamino group or an alkoxy group located at the 4th and 7th positions of the phenanthroline ring, wherein the dialkylamino group is a dialkylamino group having an alkyl group having 1 to 10 carbon atoms, and the alkoxy group is a methoxy group or an ethoxy group; m 4 、m 5 All represent 1.
25. A method for producing an organic thin film, characterized in that: It includes the following steps: A step of forming a monolayer film on a surface to be formed, wherein the monolayer film comprises a first material and a second material for transporting electrons, wherein the first material is a phenanthroline compound having a structure represented by the following general formula (2); or a step of sequentially forming a film containing the first material and a film containing the second material on a surface to be formed, In the general formula (2), R 4 , R 5 are the same or different, and represent a dialkylamino group or an alkoxy group located at the 4th and 7th positions of the phenanthroline ring, wherein the dialkylamino group is a dialkylamino group having an alkyl group having 1 to 10 carbon atoms, and the alkoxy group is a methoxy group or an ethoxy group; m 4 、m 5 All represent 1, The second material is an organic material.
26. A method for producing an organic thin film, characterized in that: The method comprises the steps of forming a film containing a first material on a surface to be formed containing a second material, wherein the first material is a phenanthroline compound having a structure represented by the following general formula (2), and the second material is an organic material that transports electrons. In the general formula (2), R 4 , R 5 are the same or different, and represent a dialkylamino group or an alkoxy group located at the 4th and 7th positions of the phenanthroline ring, wherein the dialkylamino group is a dialkylamino group having an alkyl group having 1 to 10 carbon atoms, and the alkoxy group is a methoxy group or an ethoxy group; m 4 、m 5 All represent 1.
Citation Information
Patent Citations
New boron compounds, their production method, and functional electronic device using them
JP2009155325A
Photosensitive composition for optical decoloring layer
JP2010230995A
Microbicidal composition
JP2011006457A
Microbicidal composition
JP2011006458A
Boron-containing compound and method for producing the same
JP2011184430A